Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Experimental and analytical investigations of composite girders with CSW-CFST chord-UHPC slab under impact loading - Wei Xian; Shuang-Shuang Li; Wen-Da Wang; Yan-Li Shi; Wei-Hong Wu; Wensu Chen (Engineering Structures, 2026)

Lateral impact performance of concrete-encased concrete-filled steel tubular (CECFST) members after exposure to fire: Tests and analysis - Yuan Zheng; Wen-Da Wang; Sun-Hang Ji; Yan-Li Shi; Wei Xian; Rui Wang (Engineering Structures, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Construction of sea bass (Lateolabrax japonicus) powder/κ-carrageenan composite gels: Nonlinear rheological properties, IDDSI classification, and gelation mechanisms - Yin-Yin Lv; Tian-Qi Zhou; Xian-Hao Zhang; Miao-Miao Luo; Yi-Nan Du; Ce Wang; Bin Lai; Da-Ming Fan; Na-Na Zhang; Heng Jiang; Jia-Nan Yan; Hai-Tao Wu (Food Chemistry, 2026)

A parametric model for generating dynamic lighting electricity profiles in shopping malls using large-scale longitudinal data - Jingjing Ma; Yi Wu; Xuyuan Kang; Da Yan (Energy and Buildings, 2026)

Tough lean-water hydrogel electrolyte with enhanced ionic conductivity for high-performance aqueous zinc-ion batteries - Liang Chen; Julu Qiu; Shuyi Guo; Da Shi; Qingrong Wang; Yan Wang; Jialu Chen; Liubin Zhao; Ping Rao; Wenshan Ren (Chemical Engineering Journal, 2026)

Reference year methods under climate change: A comprehensive review of evolution, applications, and future directions - Jiwei Zou; Shujie Yan; Jing Kong; Abhishek Gaur; Lin Wang; Da Yan; Zheng Tan (Building and Environment, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

The bidirectional interplay between arbuscular mycorrhizal fungi and root hairs: A review of functional complementarity - Jing-Jing Tan; Yang Lü; Fábio Sérgio Barbosa da Silva; Ying-Ning Zou; Qiang-Sheng Wu; Chun-Yan Liu (Rhizosphere, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Dynamic responses of CFST column to steel beam joints subjected to impact loading - Wei Xian; Wensu Chen; Yan-Li Shi; Wen-Da Wang; Long Zheng; Jun-Liang Yao (Engineering Structures, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Investigation of changes in microbial communities and metabolites for the nutrient re-utilization of fermented agricultural wastes in watermelon - Tong-Lu Wei; Yan-Ge Li; Mao-Song Pei; Hai-Nan Liu; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Biomass and Bioenergy, 2026)

Mechanism-oriented Object–Environment–Emotion (OEE) framework for urban flood disaster assessment using multimodal social media - Yating Fan; Yuefan Li; Zhihao Shen; Da Kuang; Yu Yan (Sustainable Cities and Society, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Climate change during the early Middle Jurassic: Evidence from coal-bearing strata of the Ordos Basin - Nian-De Shang; Jing-Jing Liu; Shi-Feng Dai; Ian T. Graham; Qiu-Chan Han; Rong-Kun Jia; Jia-Wei Feng; Meng-Da Yao; Yan Wang (Palaeoworld, 2026)

Natural deep eutectic solvents assisted the encapsulation of curcumin in gellan gum hydrogels - Yu-Nan Pan; Jia-Cheng Liu; Lin-Da Zhang; Bin Lai; Ce Wang; Jia-Nan Yan; Hai-Tao Wu (Food Research International, 2026)

A hierarchical thermal preference structure for understanding satisfaction in multi-occupant offices under cooling season conditions - Jingjing An; Qixuan Li; MingYang Qian; Da Yan; Ruosa Wu; Xin Zhou (Building and Environment, 2026)

Mercury Bioaccumulation in Non-predatory Fish from an Indigenous Protected Area: Implications for Human Health in the Southern Amazon Basin - Yan Costa Gonçalves; Priscila Rodrigues de Siqueira; Iara da Costa Souza; Julieta Griboff; Magdalena Victoria Monferrán; Daniel Alberto Wunderlin; Manoela Maria Ferreira Marinho; Marisa Narciso Fernandes; Diana Amaral Monteiro (Exposure and Health, 2026)

HTLV-1 infection in patients with neurological manifestations in Northeast Brazil - Artur Fernando Soares da Silva; Yan Charles da Silva Bastos; Juliana Tiemi Oikawa; Ana Eliza Vargas Eskinazi Sant’Anna; Gabriel Galindo Cunha; Clarice Neuenschwander Lins de Morais; Elisa de Almeida Neves Azevedo; Maria Rosângela Cunha Duarte Coêlho (Journal of NeuroVirology, 2026)
Human T-lymphotropic virus type 1 (HTLV-1) infection is associated with a broad spectrum of neurological manifestations, including conditions that may precede the development of HTLV-1–associated myelopathy/tropical spastic paraparesis (HAM/TSP). This analytical, descriptive cross-sectional study aimed to estimate the prevalence of HTLV-1 infection and describe associated sociodemographic, socioeconomic, behavioral, and clinical characteristics among patients with neurological disorders followed at a tertiary public hospital in Northeast Brazil between 2024 and 2025. A total of 300 patients underwent serological screening using an enzyme-linked immunosorbent assay (ELISA) with a commercial kit (DiaSorin Murex HTLV-1 + 2). Samples with positive or indeterminate results underwent DNA extraction and molecular confirmation by polymerase chain reaction (PCR) to differentiate viral types. Three patients tested positive for HTLV-1, resulting in an overall prevalence of 1.0%. All HTLV-1-positive individuals were women aged 43 to 72 years with low educational attainment and income. Univariate analyses identified significant associations with injection drug use, history of blood transfusion, and family history of HTLV-1 infection. Clinically, HTLV-1-positive patients presented heterogeneous neurological manifestations, ranging from urinary dysfunction and lower limb sensory and motor impairment to musculoskeletal and inflammatory symptoms. These findings highlight the broad spectrum of neurological involvement associated with HTLV-1 infection. Early identification of HTLV-1 may contribute to improved clinical management and inform public health strategies.

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Depth-dependent attachment and transport of bacteriophages MS2 and ΦX174 in saturated soils: Impacts of silt and clay fraction - Xue-yan Hao; Ying Han; Ying Song; Rong-xuan Xu; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Copolymer hydrogel formed by κ-carrageenan and chickpea protein amyloid fibrils: From rheological properties to regulation of aggregation morphology - Lin-Da Zhang; Xiao-Lei Zang; Yu-Nan Pan; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Hydrocolloids, 2026)

Vegetation index trends under contrasting land-use occupation in Brazilian savannas: a paradox between the established region and the agricultural frontier - Yan Breno Azeredo Gomes da Silva; Lênio Soares Galvão; Fábio Marcelo Breunig; Lucas Batista de Oliveira (Environmental Monitoring and Assessment, 2026)
Long-term trajectories of the Normalized Difference Vegetation Index (NDVI) provide insights into ecosystem changes associated with vegetation productivity and land degradation. However, their interpretation may depend on land-use history. Here, we analyzed NDVI trajectories from Moderate Resolution Imaging Spectroradiometer (MODIS) data (2000–2022) across two contrasting regions in the Brazilian Cerrado: an established agricultural region and an expanding frontier. We evaluated whether NDVI trends differ between regions as a function of land-use dynamics and environmental/climatic conditions. NDVI trajectories were derived using Trends.Earth and correlated with MODIS Gross Primary Production (GPP). Common and region-specific trend drivers were analyzed using binary logistic regression and Wald-type Z tests. Results revealed a remote-sensing paradox. Despite pronounced differences between regions, the primary common driver of NDVI decline was the native savanna conversion to croplands and pastures. Paradoxically, the established agricultural region, where most clearing predated satellite observations, was the most stable, showing the smallest pixel proportion of NDVI decrease (7%) and the highest proportion of increase (52%). In contrast, the agricultural frontier, where native vegetation dominates and clearing largely coincided with satellite observations, showed greater NDVI decline (16%) and smaller increases (37%). Positive NDVI–GPP relationships were weaker in the established region. Region-specific drivers included precipitation, soil sand content, and fire frequency. Longer agricultural use duration contributed to NDVI increases, likely reflecting management practices that mask underlying degradation. Our findings indicate that NDVI-based assessments of land degradation in the Cerrado must consider early land-use history and agricultural management relative to the period of satellite observations.

Association between COVID-19 booster vaccination and influenza mortality: a nationwide retrospective cohort study using the SIVEP-Gripe database in Brazil - Daniele Melo Sardinha; Natália Melazo Machado Neves; Tamires de Nazaré Soares; Marcos Jessé Abrahão Silva; Lidiane Assunção de Vasconcelos; Luany Rafaele da Conceição Cruz; Karina Faine Freitas Takeda; Natasha Cristina Oliveira Andrade; Suziane do Socorro dos Santos; Felipe Costa Soares; Neiva José da Luz Dias Júnior; Yan Corrêa Rodrigues; et al. (Immunologic Research, 2026)
To identify clinical and epidemiological predictors of mortality among patients hospitalized with laboratory-confirmed influenza in Brazil during 2024, and to evaluate the association of vaccination and antiviral therapy with clinical outcomes. We conducted a nationwide retrospective cohort study using the Brazilian SIVEP-Gripe surveillance database. All hospitalized patients with RT-PCR–confirmed influenza and known outcomes were included. Multivariable logistic regression was initially performed to explore predictors of mortality. To more rigorously assess the association between COVID-19 booster vaccination and mortality, a propensity score–based inverse probability of treatment weighting (IPTW) approach was applied, with weights truncated at 10. E-values were calculated to assess robustness to unmeasured confounding. A total of 15,995 hospitalized influenza cases were included, with an overall case fatality rate of 12.1%. Influenza A predominated (88.0%) and was associated with higher mortality than Influenza B. In IPTW-weighted models, COVID-19 booster vaccination remained independently associated with reduced mortality (OR 0.90, 95% CI 0.84–0.97; p = 0.007). Additional risk factors included dyspnea, respiratory distress, and low oxygen saturation, as well as comorbidities such as obesity, diabetes, liver disease, and immunosuppression. Protective factors included influenza vaccination (OR 0.77) and oseltamivir use (OR 0.81). The model demonstrated good discrimination (AUC = 0.81, 95% CI 0.80–0.82). The E-value for the booster association was 1.46, indicating moderate robustness to unmeasured confounding. Influenza mortality in Brazil is primarily driven by age, comorbidities, and clinical severity at presentation, but is significantly mitigated by vaccination and antiviral therapy. The observed association between COVID-19 booster vaccination and reduced mortality suggests a possible heterologous immune effect, although causality cannot be established. These findings support integrated immunization strategies targeting multiple respiratory pathogens.

Micro/nanoplastics and lithium iron phosphate at environmentally relevant dose triggers hepatic fibrosis: Unseen risks of global renewable energy - Peng Xia; Ruqin Shen; Xue Zhang; Zehua Yan; Shaoda Zhou; Hongli Tan; Yan Zhang; Da Chen; Yongfeng Deng (Journal of Hazardous Materials, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

Reaction mechanisms and catalyst design principles of MOFs and their derivatives in the electrocatalytic nitrate reduction for ammonia production - Huaiyu Zhou; Qing Wang; Yan Pan; Shuo Pan; Da Cui; Jingru Bai (Journal of Environmental Chemical Engineering, 2026)

Short-term ecotoxicogenomic responses reveal early molecular mechanisms of pyraclostrobin toxicity in honey bees - Jaine da Luz Scheffer; Isabella Cristina de Castro Lippi; Yan Souza Lima; Juliana Sartori Lunardi; Marcus Vinícius Niz Alvarez; Ricardo de Oliveira Orsi (Environmental Toxicology and Pharmacology, 2026)

Resampling native bee communities over 30 years showed stable trends along a tropical forest disturbance gradient - Qiaoyi Nong; Xiaojian Chen; Molin Hou; Da-Rong Yang; Michael C. Orr; Bai-Ge Miao; Cheng Wenda; Yan-Qiong Peng (Journal of Insect Conservation, 2026)

Susceptibility and Clinicopathological Findings in Three Amazonian Fish Species Experimentally Infected with Lactococcus spp.: A Preliminary Study - Angélica Emanuely Costa do Rosário; Francisco Yan Tavares Reis; Angelo Carlo Chaparro Barbanti; Érik José Carvalho da Costa; Cynthia Rafaela Monteiro da Silva Maia; Suzana Kotzent; Sóstenes Apolo Correia Marcelino; Felipe Pierezan; Gustavo Moraes Ramos Valladão; Ronald Kennedy Luz; Henrique César Pereira Figueiredo; Silvia Umeda Gallani; et al. (Fishes, 2026)
Bacterial diseases cause significant losses in the aquaculture of Amazonian fishes (Arapaima gigas, Brycon amazonicus, and Colossoma macropomum). Lactococcosis-causing bacteria (LCB) have emerged as important pathogens in global aquaculture, and although they have already been isolated from these fish species, their pathogenic role remains unconfirmed. This study evaluated the susceptibility of three Amazonian fish species to Lactococcus spp. through experimental infection and performed a detailed examination of the associated pathological damage. Lactococcus formosensis, L. garvieae, and L. petauri strains were used to intracoelomically infect juvenile Amazonian fish. Following infection, the fish were monitored for 15 days to evaluate clinical signs and mortality. Clinical signs were observed in the L. garvieae-challenged A. gigas, with one fish dying at five days post-infection. The remaining experimental animals, regardless of fish species, survived the challenge. All mortalities and surviving fish at the end of the trial underwent bacteriological and histopathological examinations. Bacteriological examination confirmed bacterial re-isolation from asymptomatic animals in the L. garvieae-challenged A. gigas (2/7) and L. formosensis-challenged C. macropomum (3/7) groups using MALDI-TOF MS and multiplex qPCR analysis. No bacterial growth or histological alterations were observed in the control groups or in the groups infected with L. petauri. Microscopic examination revealed L. garvieae-induced fibrinoid-necrotic hepatitis, lymphohistiocytic myocarditis, and myositis in diseased or asymptomatic A. gigas, while L. formosensis caused lymphohistiocytic pericarditis in surviving C. macropomum. These findings provide preliminary evidence suggestive of susceptibility of A. gigas and C. macropomum to infection by L. garvieae and L. formosensis, respectively, highlighting their potential to act as asymptomatic carriers. Furthermore, the histopathological findings were suggestive of species-associated lesion patterns of piscine lactococcosis in Amazonian fish, rather than indicative of high mortality.

Sesquiterpene-rich n -hexane extracts from Aspidosperma subincanum Mart.: anti- Xanthomonas citri activity, acetylcholinesterase inhibition and insights into molecular docking - Hindenburg C. G. da Costa; Jaciel G. dos Santos; Cassia C. Fernandes; Cibele S. Minafra; Anna L. O. Santos; Daniela S. Gonçalves; Carlos H. G. Martins; Matheus R. S. Melo; Fernanda F. Noronha; Denise C. Tavares; Yan R. Robles; Antônio E. M. Crotti; et al. (Natural Product Research, 2026)

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

Bio-inspired White Tablet Coating Film Without Titanium Dioxide - Yutong Tian; Shihao Song; Yaojie Shi; Li Yuan; Jiaqi Yan; Da Wang; Luping Sha; Li Yang (Pharmaceutical Research, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Local ecological knowledge with stewardship sustains medicinal plants used by ethnic minorities in China - Da-Cheng Hao; Yan Wang; Dinghao Deng; Zhiduan Chen; Richard W. Spjut; Peigen Xiao (Trends in Ecology & Evolution, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Integrated multi-dimensional framework for water conservation capacity evaluation and attribution in the Yellow River water conservation area - Da Xu; Ruochen Sun; Qingyun Duan; Zhi Liang; Xuejia Wang; Yan Ma (Journal of Hydrology, 2026)

Novel kinked connection component (KCC) for enhanced progressive collapse performance in CFST column–steel beam joints - Long Zheng; Yu-Chen Zhang; Yan-Li Shi; Wen-Da Wang; Yin-Quan Yu (Engineering Structures, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Whole-genome Resequencing Reveals the Sex Determination System and Develops a Sex-specific Marker in Fat Greenling (Hexagrammos otakii) - Duan Liao; Yangqing Zhang; Chunlong Miao; Shuo Li; Weijing Li; Chen Li; Ivana Felipe da Rosa; Lucas Benites Doretto; Yuyan Liu; Qian Wang; Kaiqiang Liu; Hong-Yan Wang; et al. (Marine Biotechnology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

High prevalence of posttraumatic stress disorder in survivors of aneurysmal subarachnoid hemorrhage: a 6-month follow-up screening study - Isabela Costola Windlin; Bruno Braga Sisnando da Costa; Pedro Henrique Mouty Rabello; Ilan David Friedmann; Yan Luca de Abreu Alves Jacinto; Davi Jorge Fontoura Solla; Carlos Gilberto Carlotti Jr.; Eberval Gadelha Figueiredo (Acta Neurologica Belgica, 2026)
Background Posttraumatic stress disorder (PTSD) is increasingly recognized as a sequela of subarachnoid hemorrhage (SAH); however, its prevalence and clinical correlates remain understudied. This study assessed the prevalence of PTSD symptoms and associated psychological symptoms among survivors of SAH. Methods A 6-month prospective analysis of 45 SAH survivors from the GASH trial (NCT03569540) was conducted. PTSD symptoms were evaluated using the Screen for Posttraumatic Stress Symptoms (SPTSS), with concurrent assessment of anxiety/depression (Hospital Anxiety and Depression Scale, HADS) and functional outcomes (modified Rankin Scale). Results At six months post-SAH, 55,56% ( n = 25) of patients met the SPTSS criteria for significant PTSD symptoms. Avoidance (mean score: 23,36 ± 11,75) and hyperarousal (19,52 ± 10,22) were the most prominent symptoms. PTSD was strongly associated with concurrent anxiety (HADS-A ≥ 7; p p Conclusion Nearly half of SAH survivors screened positive for PTSD-related symptoms within six months, with avoidance behaviors predominating. The high comorbidity of anxiety and depression underscores the necessity for integrated neuropsychiatric care in SAH follow-up protocols.

Voronoi linkage between mismatching voting stations and census tracts in analyzing the 2018 Brazilian presidential election data - Lucas da Cunha Godoy; Marcos Oliveira Prates; Jun Yan (Spatial Statistics, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Precooling effectiveness in residential buildings during heatwaves with power outages: A sensitivity and parametric analysis - Xue Liu; Hao Tang; Xuyuan Kang; Pengyuan Shen; Xin Zhou; Da Yan (Building and Environment, 2026)

Downscaling prediction of urban wind environment based on PBMs and hybrid MLP-CNN model - Xiaohan Shen; Ruolan Sun; Gerui Sui; Rongmao Xu; Xin Zhou; Da Yan; Jingjing An (Urban Climate, 2026)

Beyond honey bees: Stingless bees exhibit greater sensitivity to pesticides with implications for risk assessment - Isabella Cristina de Castro Lippi; Cooper Schouten; Yan Souza Lima; Guilherme Duarte Figueiredo de Souza; Iloran do Rosário Corrêa Moreira; Jaine da Luz Scheffer; Aline Astolfi; Ricardo de Oliveira Orsi (Pesticide Biochemistry and Physiology, 2026)

The first cranium of Postschizotherium (Pliohyracidae, Hyracoidea) from the Lower Pleistocene of China - Lu-Da Xing; Xiao-Bing Wang; Martin Pickford; Yan-Jie Chen; Jiao Ma; Shu-Qiong Wang; Yi-Yang Liu; Shi-Qi Wang (Palaeoworld, 2026)

Unlocking inherent superoxide production from potassium peroxoborate for efficient PAHs degradation - Jiajie Zhou; Shaohong Wang; Yan Tian; Yingqi Wang; Guohong Liu; Da Li; Tongtong Liu; Dahong Chen; Yujie Feng (Journal of Hazardous Materials, 2026)

Energy efficiency and thermochemistry of sulfur-containing coal gangue, a coal-based solid waste - Hui-yong Niu; Chen-hong Zhou; Hai-yan Wang; Gong-da Wang; Jiu-ling Zhang; Yan-xiao Yang; Xiaodong Yu (Fuel, 2026)

Regional and temporal differences in residential occupancy patterns: A TUS-based analysis - Yuxin Lu; Xin Zhou; Shan Hu; Mingyang Qian; Da Yan (Energy and Buildings, 2026)

Urban–rural differences in residential energy-use behavior and energy-saving awareness: Evidence from a Chinese megacity - Jingjing An; Tianyi Li; Chuang Wang; Da Yan; Shan Hu (Energy and Buildings, 2026)

Catalytic conversion of fatty acid methyl esters to biofuels under mild reaction conditions - Xiaolong Yan; Lei Wang; Weimin Da; Yawen Shi; Zhaowei Tian; Zhitong Qian; Yu Sun; Xu Zhao; Xin Zhang; Weiming Zhai; Feng Liu; Yusen Yang; et al. (Chemical Engineering Journal, 2026)

Investigating the predictability of building occupancy time series using an information entropy-based approach - Xiao Wang; Xuyuan Kang; Xin Zhou; Hongsan Sun; Zhi Shuai; Da Yan (Building and Environment, 2026)

Environmental impacts of toxic elements on crop-grazing soils in areas surrounding artisanal mining in the Brazilian Amazon - Flavio Henrique Santos Rodrigues; Wendel Valter da Silveira Pereira; Yan Nunes Dias; Sílvio Junio Ramos; Paula Godinho Ribeiro; Matheus Bortolanza Soares; Marcele Farias Pereira; Antonio Rodrigues Fernandes (Environmental Geochemistry and Health, 2026)

Characterization and CLEA immobilization of Talaromyces pinophilus phytase produced in Komagataella phaffii - Rafaela Inês de Souza Ladeira Ázar; Yan da Silva Clevelares; Roberta Corsino Ferreira; Riziane Ferreira Gomes; Gabriela Piccolo Maitan-Alfenas; Valéria Monteze Guimarães (Archives of Microbiology, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

Three new flavonoid glycosides from the herbaceous stems of Ephedra intermedia - Ying Niu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Di Lu; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Product Research, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Contact with fipronil affects pollination-associated gene expression in honey bees - Yan Souza Lima; Isabella Cristina de Castro Lippi; Jaine da Luz Scheffer; Juliana Sartori Lunardi; Marcus Vinícius Niz Alvarez; Daniel Nicodemo; Samir Moura Kadri; Ricardo de Oliveira Orsi (Science of The Total Environment, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Molecular identification and characterization of a ‘Candidatus phytoplasma australasiaticum’ -related strain associated with Scaevola taccada virescence disease in China - Hai-Yan Che; Mei-Jiao Hu; Hai-Bo Long; Da-Quan Luo; Shao-Shuai Yu (Physiological and Molecular Plant Pathology, 2026)

CoFe@NiFe-LDH/CC bifunctional electrode: Mechanism and reactive oxygen species generation in the synergistic anodic oxidation and electro-Fenton processes - Bai-Chao Feng; Huai-Yuan Niu; Da-Wei Huang; Ming Yan; Cheng-Gang Niu (Journal of Cleaner Production, 2026)

EED226 treatment targets key immune genes to suppress LPS response in Chinese tongue sole splenocytes - Yangqing Zhang; Lei Lin; Duan Liao; Shengyu Zhu; Yanan Li; Lucas Benites Doretto; Ivana Felipe da Rosa; Yajun Wang; Hong-Yan Wang; Changwei Shao (Fish & Shellfish Immunology, 2026)

Long-term impact of climate change on residential cooling loads in Beijing: A multi-factor analysis of occupant behaviors and envelopes - Jingjing An; Wenyan Liu; Chuang Wang; Xin Zhou; Shan Hu; Da Yan (Energy and Buildings, 2026)

A mutually beneficial waste-to-biochar strategy: Mn-mediated dual enhancement of 5-HMF production and catalytic performance - Yan Sun; Ranxin Li; Qiubo Wang; Wen-da Oh; Mingjie Huang; Xiaohui Wu; Tao Zhou (Chemical Engineering Journal, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Facial expression portrait: A non-verbal and interactive method for soundscape assessment in urban open spaces - Yuxin Yin; Qi Meng; Wei Yan; Da Yang; Mengmeng Li (Building and Environment, 2026)

Mantle heterogeneity and complicated melt migration revealed by chemical gradients across the dunite-harzburgite sequence in the Zedong ophiolite, South Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu (Contributions to Mineralogy and Petrology, 2026)

A new polyketide from Penicillium sp. HK-G2 and its inhibitory activity against α-glucosidase - Jie Zhen Shi; Yan-Li Zhang; Jin Hua Yu; Da-Mei Wang; Dong Gan; Zhong-Tao Ding (Natural Product Research, 2025)

Boosting the electro-Fenton process with a functionalized ACF cathode: Simultaneous H2O2 production and Fe2 + regeneration for rapid bisphenol A degradation - Juntao Tang; Yuhao Wu; Guanlong Wang; Mengyi Cao; Junxi Song; Da Wang; Weiting Yu; Yan Yu; Zhiqiao He; Shuang Song (Journal of Environmental Chemical Engineering, 2025)

A Bayesian–physics integrated optimization framework for flexible building cooling under heatwave conditions - Xinyi Liu; Xue Liu; Yang Geng; Da Yan; Shan Hu; Hao Tang (Energy and Buildings, 2025)

Building microgrid profile scheduler (BMPS): A web-based open tool for operation profile dispatching towards flexible energy system design and control - Xuyuan Kang; Xiao Wang; Zhaoru Liu; Yi Wu; Xue Liu; Da Yan (Energy and Buildings, 2025)

Neutrophil extracellular trap (NET)-targeted nanoparticles alleviate myocardial ischemia–reperfusion injury in mice by inhibiting macrophage–myofibroblast transition - Da Lu; Wei Jiang; Xi Zhang; Jiangshui Liang; Meng Xiong; Changzhi Yan; Anyi Lin; Teng Ma; Feng Zhu; Yongqiang Dong (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Effects of optical scattering in aerogel glazing system on daylight illuminance and discomfort glare - Dongmei Zheng; Youming Chen; Da Yan (Building and Environment, 2025)

Receptor affinity-selective differential dynamics of membrane fusion initiation govern deltacoronavirus cross-species transmission - Da An; Qi Peng; Yong-Hao Ma; Wenguang Hong; Yi Pei; Shiyu Liu; Yan Li; Jizong Li; Yanke Shan; Yulong Yin; Bin Li; Fei Liu (Science China Life Sciences, 2025)

Combustion Behavior and Thermal Disaster Quantification of Weathered Water-Saturated Coal in an Oxygen-Poor Environment of Goaf - Hui-yong Niu; Hao-liang Zhu; Qing-qing Sun; Hai-yan Wang; Gong-da Wang; Lu-lu Sun (Natural Resources Research, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Cadmium-induced nucleus pulposus derived mesenchymal stem cells apoptosis via MAPK signaling pathway contributes to IVD degeneration - Man Hu; Yu Zhang; Wen-jie Zhao; Xin Liu; Yan-feng Zhang; Da-xu Liu; Xin-min Feng; Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

A novel framework for multi-step water level predicting by spatial–temporal deep learning models based on integrated physical models - Shuo Zhang; Da Zhang; Guoxian Huang; Jiaquan Wan; Yan Kang; Dongqing Jiang; Bo Xia; Zhonglin Zhao; Ranyu Liu (Journal of Hydrology, 2025)

Experimental and analytical investigations of prefabricated RC beam to CFST column joints subjected to beam-end impact loads - Wei Xian; Zhi-Meng Wang; Wensu Chen; Yan-Li Shi; Wen-Da Wang (Engineering Structures, 2025)

A novel interpolation method for high temporal-resolution electricity usages based on volatility quantification and pattern extraction - Yinao Zhou; Ruoxi Geng; Xuyuan Kang; Huiming Xu; Xiao Wang; Rui Li; Da Yan (Energy and Buildings, 2025)

Direct integration of covalent organic framework on β-lactose cellulose as a carrier for chromium ion-imprinted polymers with squaramide receptor - Shakeel Zeb; Rongpeng Yu; Lariel Chagas da Silva Neres; Liangyin Xiang; Zhenyu Wu; Yuxin Xie; Zuoyi Liu; Yan Liu (Desalination, 2025)

Zn (002) texture engineering via a facile corrosion method for improved anode stability - Ye Zhang; Kai Yan; Yi Jiang; Sheng-da Liu; Jia-yin Zhan; Wen-sheng Yu; Jin-xian Wang; Xiang-ting Dong; Gui-xia Liu (Chemical Engineering Journal, 2025)

Kinetically accelerated sodium storage in Na3V1.7Fe0.3(PO4)3 enabled by activation of V4+/V5+ redox couples, oxygen vacancies and carbon composite engineering - Zhenchao Bai; Rui Wang; Quan Zong; Lijing Yan; Chengbin Jin; Da Chen; Mukhammadjon Adilov; Rustam Ashurov; Khatam Ashurov; Qiaoling Kang (Chemical Engineering Journal, 2025)

Study on the role and function of RRS1 in cutaneous squamous cell carcinoma - Zhan-Yan Pan; Zhi-Nan Shi; Qiong Wu; Ting-Ting Hu; Xiao-Hui Mo; Da-Ke Dong; Qiang Ju (Tissue and Cell, 2025)

Route-specific ecotoxicogenomic responses of the honey bee Apis mellifera to imidacloprid revealed by co-expression analysis - Isabella Cristina de Castro Lippi; Juliana Afonso; Jaine da Luz Scheffer; Yan Souza Lima; Marcus Vinícius Niz Alvarez; Marina Rufino Salinas Fortes; Ricardo de Oliveira Orsi (Science of The Total Environment, 2025)

Physiological, biochemical, and transcriptomic analyses unveil the mechanisms of melatonin in improving wheat stripe rust resistance - Da-Yan Zhang; Jia-Bao Yue; Nan Wu; Yang Wu; Huai-Yu Zhang; Shu Yuan; Ming Yuan; Shozeb Haider; Yang-Er Chen (Plant Science, 2025)

Annulohypoxylon stygium, an endophyte from the marine red alga Asparagopsis taxiformis is a source of antiviral binaphthalenes - Dulce Silva; Givaldo S. da Silva; Iatã Mendonça; Victor Rufino; Yan Fernandes; Lucas Moura; Edelson Dias (Phytochemistry Letters, 2025)

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Slow-released corrosive charge of zerovalent iron rendered superior Fenton-like catalysis: The tailored electron generation, transfer and utilization derived from spatial MoS2 encapsulation - Wei Da; Chi Zhang; Ai-Yong Zhang; Xianhui Yan; Cheng Chen; Lyumeng Ye (Journal of Hazardous Materials, 2025)

Smart construction of 8N-CuO for efficient peroxymonosulfate (PMS) activation: The synergistic effect of 8N-CuO-induced non-radical/radical pathways - Linglong Shi; Da Li; Shuangzhen Guo; Lihong Zhang; Jiaxin Bai; Mengqi Li; Sizhe Peng; Meiqi He; Yan Li; Yu Liu (Journal of Environmental Chemical Engineering, 2025)

Machine learning and causal inference for disentangling air pollution reduction during the Asian Games in megacity Hangzhou - Fan Zhang; Renchang Yan; Xianman Ye; Luolan Fei; Yaofu Zhu; Xiyao Chen; Shupeng Zhu; Bing Qi; Da Xu; Weijun Li (Environmental Pollution, 2025)

Development and evaluation of cooling tower performance prediction using physics-informed neural networks - Zehongyu Kang; Xin Zhou; Da Yan; Jingjing An (Energy and Buildings, 2025)

Leveraging reinforcement learning for optimal control of chiller plant with complex hydraulic and thermodynamic characteristics - Xiao Wang; Huiming Xu; Cheng Fan; Shengyu Tan; Xuyuan Kang; Yang Shi; Da Yan (Energy and Buildings, 2025)

Multidimensional mechanism investigation on improving the pretreatment performance and enzymatic saccharification of bamboo with choline chloride-based deep eutectic solvents - Yu Sheng; Yao-yao Jin; Hai-yan Yang; Zheng-jun Shi; Chun Shi; Da-wei Wang; Tao-hong Li; Jing Yang (Chemical Engineering Journal, 2025)

Ten questions on building stock modeling to inform energy efficiency and sustainability - Tianzhen Hong; Jeetika Malik; Jared Langevin; Zhaoru Liu; Da Yan (Building and Environment, 2025)

Ten questions concerning calibrating building energy simulation models - Adrian Chong; Da Yan; Kaiyu Sun; Sicheng Zhan; Siyu Cheng; Yi Wu; Yixing Chen; Tianzhen Hong (Building and Environment, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Pilot cultivation of a long-type variety in Pyropia suborbiculata (Bangiales, Rhodophyta) - Da-Hai Gao; Yan Zhang; Xing-Hong Yan (Journal of Applied Phycology, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

Reanalysis-data-based approach to generate urban local weather data to support building energy design in a tropical climate - Xing Zheng; Naika Meili; Shuyang Li; Huanhuan Wang; Lei Xu; Zhen Han; Martín Mosteiro-Romero; Yi Wu; Da Yan; Dengkai Chi; Guanli Feng; Rudi Stouffs (Sustainable Cities and Society, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Adverse influence of chia seed germination on iron bioaccessibility and uptake by Caco-2 cells - Mariel Caroline da Silva Menezes; Roberta Fontanive Miyahira; Kim Ohanna Pimenta Inada; Yan Fonseca dos Santos; Mônica Regina da Costa Marques Calderari; Carolina Beres; Daniel Perrone; Matilde Pumar; Marta Citelli (Food Bioscience, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Deciphering the UAV-LiDAR contribution to vegetation classification using interpretable machine learning - Tao Huang; Lei Jiao; Yingfei Bai; Jianwu Yan; Xiping Yang; Jiayu Liu; Wei Liang; Da Luo; Liwei Zhang; Hao Wang; Zhaolin Li; Zongshan Li; et al. (Computers and Electronics in Agriculture, 2025)

Flavonoids and butanolides from the bark of Machilus robusta and their bioactivities - Rui-Qi Liu; Shan-Shan Ling; Xian-Da Hu; Bing Peng; Yan-Ru Li (Phytochemistry Letters, 2025)

Influence of AC supply modes with different levels of energy sufficiency on cooling energy consumption in urban residential buildings - Wenyi Wei; Yi Wu; Jinjing Zhao; Da Yan; Jingjing An; Xin Zhou (Energy and Buildings, 2025)

High entropy alloy supported ruthenium single-atoms for enhanced electrochemical hydrogen evolution reaction - Yizhong Zou; Han Zhao; Wen-Da Zhang; Qingna Gong; Jiangyong Liu; Xiaoping Yang; Jing Wang; Xiaodong Yan (Chemical Engineering Journal, 2025)

Rare earth ions-reinforced polycationic gel polymer electrolytes for enhancing ionic conductivity and zinc anode interface stability in flexible zinc-air batteries - Hang Zhang; Jianrong Liang; Ziran You; Ying Gao; Yachu Song; Junjie Ge; Yanhao Duan; Xingchen Yan; Da Lei; Chuanling Si; Zhengzheng Li (Chemical Engineering Journal, 2025)

Capacity optimization and carbon-effective assessment of building micro-grids integrating PV, EV, and energy storages - Xuyuan Kang; Xiao Wang; Zhaoru Liu; Yi Wu; Xue Liu; Da Yan (Sustainable Cities and Society, 2025)

Simulation analysis on synergistic energy-saving effect of building envelope insulation and radiative cooling technology - Han Li; Jingjing An; Chuang Wang; Da Yan (Energy and Buildings, 2025)

Extracellular polymeric substance-intercalated MXene membrane for osmotic power generation - Da-Qi Cao; Kai Tang; Guri Yihuo; Yan Jin; Yi-Xuan Song; Yun-Feng Wu; Wen-Yu Zhang; Zhongguo Zhang; Ming-Guo Ma; Li Song; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

A new method for mechanical identification of unstable sliding rock - Yan Du; Hong-da Zhang; Mo-wen Xie; Yu-jing Jiang; Santos Daniel Chicas; Jing-nan Liu (Bulletin of Engineering Geology and the Environment, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Environmental and health impacts of potentially toxic elements in urban areas in the eastern Amazon - Adriele Laena Ferreira de Moraes; Wendel Valter da Silveira Pereira; Yan Nunes Dias; Sílvio Junio Ramos; Nilbia Abreu Ramos; Gerson Moreira Barros; Antonio Rodrigues Fernandes (Urban Climate, 2025)

Mitigating urban heat islands: Enhancing outdoor comfort with retro-reflective building materials through computational-fluid-dynamics analysis - Jihui Yuan; Da Yan; Xiong Xiao; Yasuhiro Shimazaki; Yupeng Wang; Zhichao Jiao; Zhengsong Lin; Marko Bizjak; Craig Farnham; Kazuo Emura (Next Research, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Three-dimensional aligned wood arrays loading with metal-organic frameworks for improved radionuclides removal - Yifan Yan; ChuanYing Wu; Qiang Guan; Da Tian; Dichen Xia; Yue He; Pengcheng Gu (Journal of Environmental Chemical Engineering, 2025)

Three-Dimensional Shallow P-wave Velocity Distribution in the Source Area of the 2021 MS6.0 Luxian Earthquake from Dense Array Seismic Imaging - Jian-xun Yang; Qi-yan Yang; Da-hu Li; Yong-ming Lu; Ping-ping Wu; Hui-li Guo; Ning-bo Jiang; Mi Gao; Heng Pan (Applied Geophysics, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

The Paeonol of Total Glucosides of White Peony Regulates the Differentiation of CD4+Treg Cells through the EP300/Foxp3 Axis to Relieve Pulmonary Fibrosis in Mice - Muyun Yan; Qing Wang; Hongzhong Yang; Da Liu; Weijun Liang; Huamei Chen (Cell Biochemistry and Biophysics, 2025)

Flexural fatigue behavior of FRP-reinforced UHPC tubular beams - Tian-Hui Fan; Jun-Jie Zeng; Xianwen Hu; Jun-Da Chen; Ping-Ping Wu; Hui-Tao Liu; Yan Zhuge (Engineering Structures, 2025)

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Mass movement hazard assessment of active coastal cliffs (Northeast Brazil) - Melvin Moura Leisner; Davis Pereira de Paula; Rodrigo Guimarães de Carvalho; Frederico de Holanda Bastos; Miguel da Guia Albuquerque; Yan Gurgel Vasconcelos; Deivid Cristian Leal-Alves; Jader Onofre de Morais (Ocean & Coastal Management, 2025)

On the occurrence and causes of long-term declines in MODIS NDVI within the savanna environment of central Brazil - Yan Breno Azeredo Gomes da Silva; Lênio Soares Galvão; Ieda Del'Arco Sanches; Lucas Batista de Oliveira (Remote Sensing Applications: Society and Environment, 2025)

Recyclable and reused peroxymalic acid pretreatment for enhancing enzymatic saccharification and ethanol production of bamboo residues - Zhen-tai Wei; Chen-kai Qiu; Hai-yan Yang; Zheng-jun Shi; Chun Shi; Da-wei Wang; Jing Yang (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Numerical analysis on fire behaviour of concrete-filled steel tubular columns after lateral impact - Sun-Hang Ji; Wen-Da Wang; Yan-Li Shi; Jing-Xuan Wang (Engineering Structures, 2025)

The efficient separation of bioactive components from Eucommia ulmoides Oliver using membrane filtration technology and its mechanisms in preventing alcoholic liver disease - Xiao-Na Le; Da-Ping Long; Shuang-Shuang Yin; Ren-Yan Qing; Zhi-Zheng Chi; Ming-Qing Gao; Ming-Qiang Zhu (Carbohydrate Polymers, 2025)

Unraveling phase-dependent variations of viral community, virus-host linkage, and functional potential during manure composting process - Zhengyuan Zhou; Songfeng Liu; Muhammad Saleem; Fei Liu; Ruiwen Hu; Hualong Su; Da Dong; Zhiwen Luo; Yongjie Wu; Yan Zhang; Zhili He; Cheng Wang (Bioresource Technology, 2025)

Toxesbium gen. nov., the first definitive member of Ernobiinae from mid-Cretaceous amber of northern Myanmar (Coleoptera: Ptinidae) - Yan-Da Li; T. Keith Philips; Di-Ying Huang; Chen-Yang Cai (PalZ, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Subchronic exposure to nonylphenol ethoxylate (NPE) induces cardiotoxicity and oxidative stress in American bullfrog tadpoles: a mechanistic approach - Yan Costa Gonçalves; Bruno Hofstatter da Silva; Camila Reis de Godoy; Francisco Tadeu Rantin; Ana Lúcia Kalinin; Diana Amaral Monteiro (Ecotoxicology, 2025)

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Polyphenolic profile, botanical origin, and radical scavenging activity of geopropolis produced by the stingless bee Melipona subnitida Ducke in northeastern Brazil - Déborah Munique Nogueira de Sousa-Fontoura; Paulo Henrique Xavier de Amorim Silva; Francisco de Assis Ribeiro dos Santos; Celso Amorim Camara; Lucas Hilario Nogueira de Sousa; Elenilson de Godoy Alves Filho; Renata Mendonça Araújo; Yan Souza Lima; Eva Monica Sarmento da Silva; Tania Maria Sarmento Silva (Food Research International, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Gelation properties and swallowing characteristics of heat-induced whey protein isolate/chia seed gum composite gels as dysphagia food - Lin Li; Yu-Qiao Wang; Lin-Da Zhang; Jia-Nan Yan; Ce Wang; Bin Lai; Hai-Tao Wu (Food Chemistry, 2025)

Enhancing whipped cream anti-freeze properties: A dual plant system with aquafaba and mung bean protein - Yan Zhan; Lai Wei; Tianai Ge; Da Chen; Li Wang; Jiang Jiang (Food Hydrocolloids, 2025)

Microbial electrochemical coupling floating treatment wetland enhanced low-carbon wastewater remediation: Driving wastewater denitrification with different current densities - Zhengyu Yan; Guohong Liu; Ye Qiu; Dongyi Li; Dahong Chen; Da Li; Yujie Feng (Chemical Engineering Journal, 2025)

Ten questions on future and extreme weather data for building simulation and analysis in a changing climate - Da Yan; Yi Wu; Jeetika Malik; Tianzhen Hong (Building and Environment, 2025)

Effect of exogenous abscisic acid on the formation and release of archeospores in Pyropia yezoensis - Li Zhang; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2025)

Targeted isolation of lignans from the roots of Anthriscus sylvestris (L.) Hoffm. by small molecule accurate recognition technology - Yan-ling Liu; Yan-gang Cao; Ya-juan Zheng; Ying Niu; Lan Chen; Xu Chen; Xin-yi Ma; Xiang-da Li; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2025)

Dynamic analysis of green technology innovation in products and processes under supply chain competition scenarios—A study based on stochastic differential game model - Rui Sun; Da-yi He; Jing-jing Yan (Journal of Environmental Management, 2025)

Physics-consistent input convex neural network-driven reinforcement learning control for multi-zone radiant ceiling heating and cooling systems: An experimental study - Xiao Wang; Xuezheng Wang; Xuyuan Kang; Bing Dong; Da Yan (Energy and Buildings, 2025)

High-Performance wave loss capability by Constructing Well-Defined hierarchical aerogel framework with strongly coupled Carbon/CeO2 interface - Yun-Xia Bai; Da-Peng Liu; Lu Zhou; Bo Cai; Pei-Yan Zhao; Hua-Long Peng; Yu Zhang; Qi-Fan Xuan; Wen-Hao Liang; Zhi-Ling Hou; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Unveiling the surface reconstruction of CoWO4 on electrocatalytic nitrate reduction reaction - Qingna Gong; Han Zhao; Wen-Da Zhang; Jing-Dong Feng; Yiguo Zhang; Ying Zhang; Jiangyong Liu; Bing Liu; Jiangwei Zhang; Xiaoping Yang; Jing Wang; Xiaodong Yan (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Critical considerations for co-administering rivaroxaban and vonoprazan: Unveiling potential pharmacokinetic interactions - Xiao-yu Xu; Zhe-yan Zhang; Xiao-dan Zhang; Jian-chao Luo; Yun-shan Zhong; Le-hao Jin; Da-peng Dai; Jian-chang Qian (Chemico-Biological Interactions, 2025)

Predictive models of tranquility in urban public open spaces based on audiovisual indicators analysis - Wei Yan; Qi Meng; Yuxin Yin; Da Yang; Mengmeng Li; Jian Kang (Building and Environment, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Experimental and numerical investigation of dynamic characteristics and safe mooring criteria of moored outfitting ships under swell conditions - Yunpeng Zhu; Xiaojun Li; Yan Zhu; Ming Wen; Hulin Chen; Xiaotong Yu; Da Chen (Ocean Engineering, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Aluminate-activated nano-SiO2 for enhancing water vapor barrier properties in polymers films: A safe and effective strategy - Chuang-Chuang Zhao; Qin-Bao Lin; Yan-Fen Chen; Huai-Ning Zhong; David Julian McClements; Da Ma (Food Packaging and Shelf Life, 2024)

Properties and environmental quality of the overburden and tailings of manganese mining in the Eastern Amazon - Ana Beatriz Rodrigues Nahum; Wendel Valter da Silveira Pereira; Gabriel Caixeta Martins; Yan Nunes Dias; Paula Godinho Ribeiro; Gabriel Negreiros Salomão; Markus Gastauer; Cecílio Frois Caldeira; Antonio Rodrigues Fernandes; Edna Santos de Souza; Roberto Dall'Agnol; Sílvio Junio Ramos (Environmental Research, 2024)

Efficient generation of Fe(IV) = O for water purification in periodate activation process: Reducing Fe orbital occupation and expanding electron transfer channel - Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Long Sui; Qian Wu; Xue-Gang Zhang; Cheng-Gang Niu; Ming Yan; Da-Wei Huang; Zhi-Liang Chen (Chemical Engineering Journal, 2024)

Long-life and highly stable Zn metal anodes achieved by Ag nano-coating via electron beam evaporation - Ye Zhang; Kai Yan; Yi Jiang; Sheng-Da Liu; Gui-Xia Liu (Chemical Engineering Journal, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

A Control Method for Path Following of AUVs Considering Multiple Factors Under Ocean Currents - Fangui Meng; Aimin Liu; Yan Hu; Da Ren; Yao Liu; Xin Zhang (Journal of Marine Science and Engineering, 2024)
To improve the path-following performance of autonomous underwater vehicles (AUVs) under ocean currents, a control method based on line-of-sight with fuzzy controller (FLOS) guidance and the fuzzy sliding mode controller (FSMC) is proposed. This method considers multiple factors affecting guidance and adaptively determines the optimal heading angle through the fuzzy controller to enhance guidance capability. Additionally, a novel FSMC based on Lyapunov stability theory is designed to suppress the influence of model uncertainty and external disturbances on the control system. Simulations and experiments of the proposed control method demonstrate that it can maintain precise tracking under disturbances, improving path-following performance metrics by more than 15%.

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

A district-level building electricity use profile simulation model based on probability distribution inferences - Xuyuan Kang; Hongyin Chen; Zhenlan Dou; Xiao Wang; Zhaoru Liu; Chunyan Zhang; Kunqi Jia; Da Yan (Sustainable Cities and Society, 2024)

The effects of polystyrene microplastics on feeding, growth, and trophic upgrading of protozoan grazers - Fengli Zhou; Yan Wang; Xiaotu Liu; Shuaishuai Xu; Da Chen; Xiaodong Wang (Science of The Total Environment, 2024)

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Quantitative index for temporal and spatial patterns of occupant behavior based on VRF big data - Mingyang Qian; Shan Hu; Yi Wu; Hua Liu; Da Yan (Energy and Buildings, 2024)

A novel photocurable polymeric solid–solid phase change material for intelligent temperature regulators - Meiqi Liu; Zhaowen Huang; Akbar Bashir; Yichi Zhang; Haixia Qian; Xing Ouyang; Yan Hu; Haibin Chen; Da-Zhu Chen (Chemical Engineering Journal, 2024)

Boosting oxygen storage capacity of Fe-Cu bimetallic catalysts through sulfide modification for efficient and selective molecular oxygen activation - Yan Sun; Zhicheng Wang; Xiaohui Wu; Wen-Da Oh; Mingjie Huang; Tao Zhou (Chemical Engineering Journal, 2024)

Recent advances in shellfish toxin biosensing technologies: Micro/nano molecule- and cell-based biosensors - Ruobing Liu; Qilin Pei; Tao Sun; Fei Xu; Xi Shao; Juan Liu; Zedong Yan; Dan Wang; Yulan Tian; Da Jing (Trends in Food Science & Technology, 2024)

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

A novel quantitative method of heatwave classification for building resilience analysis - Xue Liu; Zhaoru Liu; Yi Wu; Shan Hu; Fan Bu; Jingjing An; Xin Zhou; Da Yan (Sustainable Cities and Society, 2024)

Analysis of stage parameters of low-temperature oxidation of water-soaked coal based on kinetic principles - Yun-chuan Bu; Hui-yong Niu; Gong-da Wang; Tian Qiu; Yan-xiao Yang; Lu-lu Sun (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Two undescribed monoterpenoids from the fruit of Gardenia jasminoides Ellis - Di Lu; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Xiang-Da Li; Xin-Yi Ma; Ying Niu; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Sea surface carbon dioxide during early summer at the Tuandao nearshore time series site - Lu Cao; Yongqi Qiu; Liang Xue; Yingying Zhang; Shuwei Zhang; Ning Wu; Da Yuan; Quanlong Li; Zheng Zhao; Ning Wang; Yan Zhou; Wei Yang; et al. (Marine Environmental Research, 2024)

Low-temperature phase stability in calc-alkaline granitic systems and significance for cold granites - Marize Muniz da Silva; Yan Lavallée; Luiz Pereira; François Holtz (Lithos, 2024)

Petrogenesis of the pyroxenitic Moho transition zone in the Zedong ophiolite, Southeastern Tibet - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Liang-Liang Zhang; Chang Zhang; Tong Liu; Bo-Da Liu; Wei-Qi Zhang; Yin-Zheng Lin; Wen-Bin Ji (Lithos, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Impact of plant and animal proteins with transglutaminase on the gelation properties of clam Meretrix meretrix surimi - Lin-Da Zhang; Lin Li; Qian Zhang; Yu-Qiao Wang; Yue Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Bioscience, 2024)

Species-level understanding of the bacterial community in Daqu based on full-length 16S rRNA gene sequences - Pei-Jie Han; Liang Song; Zhang Wen; Hai-Yan Zhu; Yu-Hua Wei; Jian-Wei Wang; Mei Bai; Lu-Jun Luo; Ju-Wei Wang; Shen-Xi Chen; Xiao-Long You; Da-Yong Han; et al. (Food Microbiology, 2024)

How urban–rural differences and ageing affect residents’ occupancy patterns – An empirical study based on China national time use survey - Xin Zhou; Jinjing Zhao; Shan Hu; Da Yan (Energy and Buildings, 2024)

Regulating the Ni-O bond length by constructing Ni(OH)2/CNTs heterostructure for enhanced nucleophile electrocatalytic oxidation - Ming Chen; Yizhong Zou; Han Zhao; Wen-Da Zhang; Qingna Gong; Jiangyong Liu; Jing Wang; Xiaodong Yan (Chemical Engineering Journal, 2024)

The effects of dietary supplementation of ginseng stem and leaf saponins on the antioxidant capacity, immune response, and disease resistance of crucian carp, Carassius auratus - Ying-da Wang; Xin Meng; Yong-chao Guan; Ze-lin Zhao; Luo-tao Tao; Jin-shuo Gong; Xin-lan Liu; Yan Zhao; Xiao-feng Shan (Fish Physiology and Biochemistry, 2024)

Effects of cadmium on the intestinal health of the snail Bradybaena ravida Benson - Yan-Mei Da; Shun-Shun Li; Yan-Qi Li; Le-Yu Deng; Ming-Jun Li; Tao Huang; Qing-Ye Sun; Jazbia Shirin; Guo-Wei Zhou (Ecotoxicology, 2024)

Effect of fracture structure on heat transfer in heat pipes in a submarine hydrothermal reservoir - Gaowei Yi; Yan Li; Da Zhang; Shiqiao Zhou (Computational Geosciences, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Bonding-slip behaviour of steel-concrete interfaces in CFDST members with PBL ribs - Yan-Li Shi; Jia-Xing Ren; Jia-Hao Fan; Wen-Da Wang; Hai-Cui Wang (Engineering Structures, 2024)

Deviation entropy-based dynamic multi-model ensemble interval prediction method for quantifying uncertainty of building cooling load - Changcheng Chen; Jingjing An; Xin Zhou; Chuang Wang; Han Li; Da Yan (Energy and Buildings, 2024)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Food contamination with fipronil alters gene expression associated with foraging in Africanized honey bees - Yan Souza Lima; Isabella Cristina de Castro Lippi; Jaine da Luz Scheffer; Juliana Sartori Lunardi; Marcus Vinícius Niz Alvarez; Samir Moura Kadri; Ricardo de Oliveira Orsi (Environmental Science and Pollution Research, 2024)

Advanced analysis of operating parameters utilizing big data to improve building cooling equipment energy efficiency standards - Yi Wu; Shan Hu; Mingyang Qian; Jianguo Xiong; Da Yan (Sustainable Cities and Society, 2024)

Intake of imidacloprid in lethal and sublethal doses alters gene expression in Apis mellifera bees - Isabella Cristina de Castro Lippi; Jaine da Luz Scheffer; Yan Souza de Lima; Juliana Sartori Lunardi; Aline Astolfi; Samir Moura Kadri; Marcus Vinícius Niz Alvarez; Ricardo de Oliveira Orsi (Science of The Total Environment, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Evaluating the sensitivity and robustness of occupancy models for building energy simulation during design - Eikichi Ono; Zeynep Duygu Tekler; Khee Poh Lam; Yuan Jin; Da Yan; Adrian Chong (Building and Environment, 2024)

Behavioral and electrophysiological study in Colossoma macropomum treated with different concentrations of Nepeta cataria oil in an immersion bath revealed a therapeutic window for anesthesia - Murilo Farias dos Santos; Lorena Meirelis do Nascimento; Clarissa Araújo da Paz; Tays Mata Câmara; Yan Kenzo Monteiro Motomya; Rayllan da Cunha Ferreira; Yris da Silva Deiga; Erika Monteiro; Sildiane Martins Cantanhêde; Lílian Lund Amado; Moisés Hamoy (Fish Physiology and Biochemistry, 2024)

Numerical study on the coupling effect of river attributes and riverside building forms on the urban microclimate: A case study in Nanjing, China - Yuxie Zhou; Yuxin Lu; Xin Zhou; Jingjing An; Da Yan (Sustainable Cities and Society, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

A new nuclear phylogeny of the tea family (Theaceae) unravels rapid radiations in genus Camellia - Yujing Yan; Rute R. da Fonseca; Carsten Rahbek; Michael K. Borregaard; Charles C. Davis (Molecular Phylogenetics and Evolution, 2024)

Cyclic behavior of laminated bio-based connections with slotted-in steel plates: Genetic algorithm, deterministic neural network-based model parameter identification, and uncertainty quantification - Da Shi; Yongjia Xu; Cristoforo Demartino; Yan Xiao; Billie F. Spencer (Engineering Structures, 2024)

A novel acceleration approach to shadow calculation based on sunlight channel for urban building energy modeling - Zhaoru Liu; Xin Zhou; Xiaohan Shen; Hongsan Sun; Da Yan (Energy and Buildings, 2024)

The effect of extracellular polymeric substances on MICP solidifying rare earth slags and stabilizing Th and U - Chang-xiong Zou; Zhen-bo Sun; Wei-da Wang; Tan Wang; Yan-xin Bo; Zhe Wang; Chun-li Zheng (World Journal of Microbiology and Biotechnology, 2024)

Establishing quality evaluation standards for pomelo fruit: The role of harvesting time and appearance characteristic - Xiaojun Yan; Muhammad Atif Muneer; Mengting Qin; Jie Ou; Xiaohui Chen; Zhiyuan He; Yedong Liu; Zhihan Cheng; Da Su; Rongrong Liu; Liangquan Wu (Postharvest Biology and Technology, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

A novel method for underactuated UUV tracking unknown contour based on forward-looking sonar - Zheping Yan; Xuyu Min; Da Xu; Dong Geng (Ocean Engineering, 2024)

Cretaceous beetles of the Jinju Formation (Coleoptera): An overview of the Jinju Formation, its coleopteran diversity, and past and future research - Soo Bin Lee; Yan-Da Li; Chenyang Cai; Michael S. Engel; Gi Soo Nam; Jong Kyun Park; André Nel; Josh Jenkins Shaw; Corentin Jouault; Andrei Legalov; Robin Kundrata (Journal of Asia-Pacific Entomology, 2024)

A novel shadow calculation approach based on multithreaded parallel computing - Xin Zhou; Xiaohan Shen; Zhaoru Liu; Hongsan Sun; Jingjing An; Da Yan (Energy and Buildings, 2024)

Artisanal mining of monazite and cassiterite in the Amazon: Potential risks of rare earth elements for the environment and human health - Pedro Paulo da Costa Alves Filho; Wendel Valter da Silveira Pereira; Yan Nunes Dias; Adriele Laena Ferreira de Moraes; Flavio Henrique Santos Rodrigues; Sílvio Junio Ramos; Edna Santos de Souza; Anna Maria Fontes do Amaral; Antonio Rodrigues Fernandes (Environmental Management, 2024)

Potassium peroxoborate: A sustained-released reactive oxygen carrier with enhanced PAHs contaminated soil remediation performance - Jiajie Zhou; Yan Tian; Chen Yan; Da Li; Tongtong Liu; Guohong Liu; Dahong Chen; Yujie Feng (Journal of Hazardous Materials, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Distribution and characteristics of loess landslides induced by the 1718 Tongwei earthquake based on a field survey - Xiaobo Li; Xinghao Zhou; Da Peng; Ganglei Ouyang; Yiwen Wu; Lingyong Yan (Bulletin of Engineering Geology and the Environment, 2024)

Sedimentary Environment, Tectonic Setting, and Uranium Mineralization Implications of the Yimin Formation, Kelulun Depression, Hailar Basin, China - Fanmin Meng; Fengjun Nie; Fei Xia; Zhaobin Yan; Da Sun; Wenbo Zhou; Xin Zhang; Qing Wang (Journal of Marine Science and Engineering, 2024)
The sandstone-type uranium deposit of the Kelulun Depression is the first industrially valuable uranium deposit discovered in the Hailar Basin. This study performed a systematic examination of 17 sandstone samples from the Yimin Formation in the Kelulun Depression based on various analytical techniques. The findings of the current study were synthesized with previous research to investigate the impact of the redox conditions and the tectonic background of the source area, as well as the paleoclimatic evolution of the Yimin Formation on uranium mineralization. The elemental Mo, U/Th, V/Cr, Ni/Co, and V/(V + Ni) ratios indicate that the paleowater was in an oxygen-rich environment during the deposition of the Yimin Formation. Additionally, the C-value, Sr/Cu, Al2O3/MgO, and Rb/Sr ratios indicate that the Yimin Formation was formed in a paleoclimate characterized by arid-to-semi-arid conditions. The geochemical characteristics of the observed elements indicated that the sediment source of the Yimin Formation was mainly felsic rocks from the upper continental crust, the weathering of the rock was weak, and the tectonic background was a passive continental margin. Coffinite is distributed in the form of cementation and stellates within or around pyrite crystals, and uranium-titanium oxide is mostly distributed in an irregular granular distribution in the biotite cleavage fractures of the study area. In summary, the findings of this study reveal that the tectonic settings, provenance, uranium source, paleoclimate, and oxygen-rich paleowater of the Yimin Formation have important geological significance for the large-scale uranium mineralization of the Kelulun Depression.

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Comammox and unknown ammonia oxidizers contribute to nitrite accumulation in an integrated A-B stage process that incorporates side-stream EBPR (S2EBPR) - Yuan Yan; Jangho Lee; IL Han; Zijian Wang; Guangyu Li; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Anand Patel; Jim McQuarrie; Beverley M. Stinson; et al. (Water Research, 2024)

Exploring the impacts of heterogeneity and stochasticity in air-conditioning behavior on urban building energy models - Zhaoru Liu; Zhenlan Dou; Hongyin Chen; Chunyan Zhang; Songcen Wang; Yi Wu; Xue Liu; Da Yan (Sustainable Cities and Society, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Determining priority control toxic metal for different protection targets based on source-oriented ecological and human health risk assessment around gold smelting area - Yan Zhou; Da Ding; Yuanchao Zhao; Qun Li; Dengdeng Jiang; Zhengyong Lv; Jing Wei; Shengtian Zhang; Shaopo Deng (Journal of Hazardous Materials, 2024)

The burgeoning importance of PIWI-interacting RNAs in cancer progression - Xinpei Deng; Tianle Liao; Jindong Xie; Da Kang; Yiwei He; Yuying Sun; Zhangling Wang; Yongluo Jiang; Xuan Miao; Yixuan Yan; Hailin Tang; Lewei Zhu; et al. (Science China Life Sciences, 2024)

MdPRX34L, a class III peroxidase gene, activates the immune response in apple to the fungal pathogen Botryosphaeria dothidea - Yu-Wen Zhao; Wan-Kun Li; Chu-Kun Wang; Quan Sun; Wen-Yan Wang; Xiao-Yu Huang; Ying Xiang; Da-Gang Hu (Planta, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

A New Method for the Correction of Spectrum Drift Caused by Temperature Changes When Using a NaI(Tl) Seawater Radioactivity Sensor - Yan Shi; Yingying Zhang; Xiandong Feng; Da Yuan; Bingwei Wu; Haijie Bi (Journal of Marine Science and Engineering, 2024)
The seawater radioactivity sensor based on the NaI(Tl) scintillation crystal detection method is prone to spectrum drift due to environment temperature changes during actual measurement, which pose difficulties in the activity analysis of seawater radionuclides. This paper adopts experiment design and analysis methods to study the relationship laws between temperature and peak position channel address and between gain and the peak position channel address. On the basis of studying and summarizing the two relationship laws of the NaI(Tl) seawater radioactivity sensor, a spectrum drift correction method combining gain adjustment and spectrum processing is proposed. Laboratory air and water environment experiments verify that the peak position channel address drift after air environment correction does not exceed ±2 channels, and after water environment correction does not exceed ±1 channel. Long-term verification experiments at the seawater work site have shown that this correction method can effectively correct the spectrum drift of the NaI(Tl) seawater radioactivity sensor and meet the requirements of long-term automatic operations at sea for the measured spectrum.

Revisiting the role of Acinetobacter spp. in side-stream enhanced biological phosphorus removal (S2EBPR) systems - Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Varun Srinivasan; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Peisheng He; Anand Patel; Charles Bott; et al. (Water Research, 2024)

Activation of the cannabinoid type 2 (CB2) receptor improves cardiac contractile performance in fish, Brycon amazonicus - Yan Costa Gonçalves; Karina Carla de Francisco Campos; Eliton da Silva Vasconcelos; Beatriz Micucci D'Almeida Eça; Francisco Tadeu Rantin; Ana Lúcia Kalinin; Diana Amaral Monteiro (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Comprehensive distribution characteristics and factors affecting the migration of chromium in a typical chromium slag-contaminated site with a long history in China - Yan Zhou; Dengdeng Jiang; Da Ding; Jing Wei; Wenyi Xie; Xin Zhu; Shaopo Deng; Tao Long; Yunjin Wu (Environmental Science and Pollution Research, 2024)

Ferric uptake regulator (fur) affects the pathogenicity of Aeromonas veronii TH0426 by regulating flagellar assembly and biofilm formation - Jin-shuo Gong; Ying-da Wang; Yan-long Jiang; Di Zhang; Ya-nan Cai; Xiao-feng Shan; He Gong; Hao Dong (Aquaculture, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

Deciphering the effects of hydrological, biogeochemical and anthropogenic factors on nitrogen species in a subtropical watershed using multiple isotopes - Xiuli Yan; Xiaolan Guo; Anqi Yao; Hongyan Bao; Da-Wei Li; Jr-Chuan Huang; Junwen Wu; Li-Li Han; Shuh-Ji Kao (Journal of Hydrology, 2024)

Integrated surrogate framework for reactive transport simulation of uranium in situ leaching with generative models - Wen-gui Ji; Yue Luo; Bing Wang; Xun Li; Jin-hui Liu; Yan-hong Zhang; Da-ye Liang (Journal of Hydrology, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Mxene-based mild hyperthemia microneedle patch for diabetic wound healing - Yuci Gan; Bo Liang; Yan Gong; Lizhen Wu; Peizhe Li; Chuchen Gong; Pei Wang; Ziyou Yu; Lingling Sheng; Da-Peng Yang; Xiansong Wang (Chemical Engineering Journal, 2024)

Performance and mechanism of pilot-scale carbon fibers enhanced ecological floating beds for urban tail water treatment in optimized ecological floating beds water surface coverage - Zhengyu Yan; Dahong Chen; Ye Qiu; Dongyi Li; Chen Yan; Jiannan Li; Da Li; Guohong Liu; Yujie Feng (Bioresource Technology, 2024)

Category representation in primary visual cortex after visual perceptual learning - Zhaofan Liu; Yin Yan; Da-Hui Wang (Cognitive Neurodynamics, 2024)

Construction of a Cuproptosis-Related Gene Signature for Predicting Prognosis in Gastric Cancer - Yongli Hu; Yan Du; Zhisheng Qiu; Pengwei Bai; Zhaozhao Bai; Chenglou Zhu; Junhong Wang; Tong Liang; Mingxu Da (Biochemical Genetics, 2024)

A novel physical-feature-based approach for stochastic simulation of typical building electricity use profiles - Xuyuan Kang; Xiao Wang; Jingjing An; Xue Liu; Da Yan (Energy and Buildings, 2024)

LBM-PFM simulation of the effect of non-condensable gas on the directional crystallization of seawater - Yina Luo; Da Zhang; Han Yuan; Yan Li (Desalination, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Grazing exclusion restores soil health in Brazilian drylands under desertification process - Antonio Yan Viana Lima; Maurício Roberto Cherubin; Danilo Ferreira da Silva; Jaedson Cláudio Anunciato Mota; Francisco Gilcivan Moreira Silva; Ademir Sérgio Ferreira de Araujo; Vania Maria Maciel Melo; Jay Prakash Verma; Arthur Prudêncio de Araujo Pereira (Applied Soil Ecology, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Exploring the applications of carbon dioxide radical anion in organic synthesis - Yong-Yuan Gui; Si-Shun Yan; Wei Wang; Lin Chen; Wei Zhang; Jian-Heng Ye; Da-Gang Yu (Science Bulletin, 2023)

Targeted clearance of mitochondria by an autophagy-tethering compound (ATTEC) and its potential therapeutic effects - Shuixia Tan; Da Wang; Yuhua Fu; Huiwen Zheng; Yan Liu; Boxun Lu (Science Bulletin, 2023)

Diarylpentanoids and phenylpropanoids from the roots of Anthriscus sylvestris (L.) Hoffm - Yan-ling Liu; Yan-gang Cao; Ying Niu; Ya-juan Zheng; Xu Chen; Ying-jie Ren; Xi-ling Fan; Xiang-da Li; Xin-yi Ma; Xiao-ke Zheng; Wei-sheng Feng (Phytochemistry, 2023)

Reinforcement learning approach for optimal control of ice-based thermal energy storage (TES) systems in commercial buildings - Xiao Wang; Xuyuan Kang; Jingjing An; Hanran Chen; Da Yan (Energy and Buildings, 2023)

Distribution and characteristics of loess landslides induced by the 1654 Tianshui earthquake, Northwest of China - Xiaobo Li; Lingyong Yan; Yiwen Wu; Da Peng; Junjie Duan; Jingshan Bo (Landslides, 2023)

Pyroxenite–harzburgite sequences in the Dazhuqu ophiolite (Southern Tibet) formed through hydrous melt infiltration and melt–peridotite reaction - Zhen-Yu Zhang; Chuan-Zhou Liu; Yan Liang; Tong Liu; Chang Zhang; Bo-Da Liu; Yin-Zheng Lin; Wei-Qi Zhang; Wen-Bin Ji (Contributions to Mineralogy and Petrology, 2023)

Human and environmental exposure to rare earth elements in gold mining areas in the northeastern Amazon - Wendel Valter da Silveira Pereira; Sílvio Junio Ramos; Leônidas Carrijo Azevedo Melo; Yan Nunes Dias; Gabriel Caixeta Martins; Luana Cristina Gonçalves Ferreira; Antonio Rodrigues Fernandes (Chemosphere, 2023)

Permafrost change and its engineering effects under climate change and airport construction scenarios in northeast China - Ming Guo; Yan Lu; Wenbing Yu; Lilin Xu; Da Hu; Lin Chen (Transportation Geotechnics, 2023)

Solidification treatment of rare earth tailings by a renewable biological cementation method - Wei-da Wang; Tan Wang; Zhen-bo Sun; Yan-xin Bo; Chang-xiong Zou; Zhe Wang; Chun-li Zheng (Process Safety and Environmental Protection, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

In-situ constructed metallic Mo decorated MoS2 nanosheets on carbon cloth as excellent anode for efficient current generation and Cr(Ⅵ) removal - Da Liu; Chaoqun Xu; Chengyu Li; Wenkai Fang; Mei Yan; Hongwu Tang (Journal of Cleaner Production, 2023)

Acceleration of state–space method based on parallelization for enhancing building thermal process simulation efficiency - Fan Bu; Xuyuan Kang; Da Yan; Ruhong Wu; Hongsan Sun; Jingjing An; Xiao Wang (Energy and Buildings, 2023)

Emissions of F-gases from room air conditioners in China and scenarios to 2060 - Shan Hu; Ziyi Yang; Da Yan; Baolong Wang; Yi Jiang (Energy and Buildings, 2023)

Proposing a carbon emission responsibility allocation method with benchmark approach - Yang Zhang; Shan Hu; Da Yan; Yi Jiang (Ecological Economics, 2023)

Investigation and application of microscopic mechanism of multiple bubble movement on directional frozen crystallization of seawater - Da Zhang; Yan Li; Han Yuan (Desalination, 2023)

Photothermal effect-enhanced peroxidase-like performance for sensitive detection of organophosphorus pesticides on a visual test strip - Yiming Wang; Min Li; Zirui Wang; Jing Xu; Junjian Zhao; Zhi-Da Gao; Yan-Yan Song (Chemical Engineering Journal, 2023)

Piezoelectric self-power supply driven by ferroelastic host–guest supramolecule with considerable electromechanical conversion capability - Meng-Meng Lun; Jia-Qi Luo; Zhi-Xu Zhang; Jie Li; Li-Yan Xie; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2023)

Prescribed fire application in a Brazilian mountain environment: Changes in soil organic matter quality in the short and medium term - Yan Vidal de Figueiredo Gomes Diniz; Ana Paula Pessim de Oliveira; Tiago Paula da Silva; Eduardo Carvalho da Silva Neto; Andrés Calderin Garcia; Marcos Gervasio Pereira; Marcelo Souza Motta; Hugo de Souza Fagundes; Otavio Augusto Queiroz dos Santos; Lúcia Helena Cunha dos Anjos (CATENA, 2023)

Indicator of climate variability: low treeline displacement in arid valleys of mountain areas, China - Wei-po Yan; Qing Wang; Ya-lin Guo; Qi Hu; Min Yang; Yi-da An (Journal of Mountain Science, 2023)

Boosting photocatalytic H2 evolution on UIO-66-NH2/covalent triazine–based frameworks composites by constructing a covalent heterojunction - Shiwen Dong; Xuan Liu; Xianxian Kong; Feilong Dong; Yan Yu; Lizhang Wang; Da Wang; Zhiqiao He; Shuang Song (Environmental Science and Pollution Research, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

Microbial communities and their correlation with flavor compound formation during the mechanized production of light-flavor Baijiu - Lu-Jun Luo; Liang Song; Ying Han; Pan Zhen; Da-Yong Han; Xin Zhao; Xin Zhou; Yu-Hua Wei; Hui-Xin Yu; Pei-Jie Han; Feng-Yan Bai (Food Research International, 2023)

4-Methylbenzylidene camphor triggers estrogenic effects via the brain-liver-gonad axis in zebrafish larvae - Hongyi Xian; Zhiming Li; Rongyi Ye; Mingzhu Dai; Yu Feng; Ruobing Bai; Jie Guo; Xiliang Yan; Xingfen Yang; Da Chen; Zhenlie Huang (Environmental Pollution, 2023)

Lateral impact behaviour of post-fire steel-reinforced concrete-filled steel tubular members: Experiment and evaluation method - Sun-Hang Ji; Wen-Da Wang; Wensu Chen; Yan-Li Shi; Wei Xian (Engineering Structures, 2023)

Assessment of electricity consumption reduction potential for city-scale buildings under different demand response strategies - Chenyang Peng; Zhihua Chen; Jingjing Yang; Zhaoru Liu; Da Yan; Yixing Chen (Energy and Buildings, 2023)

Occupant behavior modules development for coupled simulation in DeST 3.0 - Xiaoyu Jia; Yiqun Pan; Mingya Zhu; Han Zhu; Zhengrong Li; Jingsi Zhang; Xiang Zhou; Song Pan; Chuang Wang; Da Yan; Zejun Wu; Huiyan Deng; et al. (Energy and Buildings, 2023)

Development of all-cellulose sustainable composites from directionally aligned bamboo fiber scaffold with high strength, toughness, and low thermal conductivity - Cheng Qian; Yu-Tian Wang; Chun Shi; Hao-Ying Wang; Hai-Yan Yang; Jing Yang; Da-Wei Wang; Zheng-Jun Shi (Chemical Engineering Journal, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Identification of watermelon H3K4 and H3K27 genes and their expression profiles during watermelon fruit development - Yang Qiao; Yan-Ge Li; Tong-Lu Wei; Hai-Nan Liu; Mao-Song Pei; Xue-Jie Zhu; Zhong-Hou Zhu; Da-Long Guo (Molecular Biology Reports, 2023)

Cold-water coral diversity along the continental shelf margin of northwestern South China Sea - Mei-Xia Zhao; Yu Zhong; Shu-Qi Zhang; Pu Guo; Da-Peng Jiang; Hong-Qiang Yan; Jian-Wen Qiu; Qi Shi; Duan-Xin Chen (Marine Environmental Research, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

A novel approach to examining the optimal use of the cooling effect of water bodies in urban planning - Zehongyu Kang; Hua Liu; Yuxin Lu; Xinyu Yang; Xin Zhou; Jingjing An; Da Yan; Xing Jin; Xing Shi (Building and Environment, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

RNA-seq analysis reveals an immunomodulatory peptide from highland barley activating RAW264.7 macrophages via TNF/NF-κB signaling pathway - Yan Liu; Xin Chen; Jia-Yi Yang; Zhi Jian Guo; Qin Wu; Li-Da Zhang; Xuan-Wei Zhou (Functional & Integrative Genomics, 2023)

Highly-specific aptamer targeting SARS-CoV-2 S1 protein screened on an automatic integrated microfluidic system for COVID-19 diagnosis - Hung-Bin Wu; Chih-Hung Wang; Yi-Da Chung; Yan-Shen Shan; Ying-Jun Lin; Huey-Pin Tsai; Gwo-Bin Lee (Analytica Chimica Acta, 2023)

Seismogenic structure of the 2020 Jiashi, Xinjiang Ms 5.4 and Ms 6.4 moderate earthquakes - Shan-Shan Liang; Guang-Wei Zhang; Xiao-Ning Huang; Li-Ye Zou; Yan-Qiong Liu; Yun-Da Ji (Applied Geophysics, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Hydroxypropyl-beta-Cyclodextrin embedded resveratrol regulates gut microbiota to prevent NAFLD via activating AMPK signaling pathway - Wenya Ke; Juan Huang; Yi Zhong; Yuhong Shi; Fen Yan; Da Huang; Yuanzi Wu; Houbing Zheng; Zuquan Weng (Food Bioscience, 2023)

High quality diet attenuated the positive association between polychlorinated biphenyls and premature mortality among middle-aged and older adults - Weigui Ni; Qingping Xue; Shanshan Zhang; Xue Yang; Shiyi Wu; Xingchen He; Yan Xiao; Wenling Chang; Ying Wen; Yichao Huang; Yi-Xin Wang; Da Chen; et al. (Environmental Research, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

Petrogenesis of Sn-related granitoids and implications for the formation of the world-class Gejiu Sn district, South China: Insights from whole-rock and accessory mineral geochemistry - Xin Li; Yuan-chuan Zheng; Yang Shen; Chang-da Wu; Pei-yan Xu; Yan-shen Yang; Lu Wang; Zeng-qian Hou (Lithos, 2023)

A theoretical model on unfrozen water content in soils and verification - Wan Xusheng; Zhu Jishuai; Pei Wansheng; Zhou Fengxi; Lu Jianguo; Yan Zhongrui; Wa Da (Journal of Hydrology, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Host insect specificity and interspecific competition drive parasitoid diversification in a plant–insect community - Ai‐Ying Wang; Yan‐Qiong Peng; James M. Cook; Da‐Rong Yang; Da‐Yong Zhang; Wan‐Jin Liao (Ecology, 2023)
Ecological interactions among plants, insect herbivores, and parasitoids are pervasive in nature and play important roles in community assembling, but the codiversification of tri‐trophic interactions has received less attention. Here we compare pairwise codiversification patterns between a set of 22 fig species, their herbivorous pollinating and galling wasps, and their parasitoids. The parasitoid phylogeny showed significant congruence and more cospeciation events with host insects phylogeny than with host plants. These results suggest that parasitoid phylogeny and speciation is more closely related to their host insects than to their host plants. The pollinating wasps hosted more parasitoid species than gallers and indicated a more intense interspecific competition among parasitoids associated with pollinators. Closer matching and fewer evolutionary host shifts were found between parasitoids and galler hosts than between parasitoids and pollinator hosts. These results suggest that interspecific competition among parasitoids, rather than resource availability of host wasps, is the main driver of the codiversification pattern in this community. Therefore, our study highlights the important role of interspecific competition among high trophic level insects in plant–insect tri‐trophic community assembling.

RNA-seq reveals the role of miR-223 in alleviating inflammation of bovine mammary epithelial cells - Yan-Xia Li; Peng Jiao; Xing-Ping Wang; Jin-Peng Wang; Fen Feng; Bin-Wu Bao; Yi-Wen Dong; Zhuo-Ma Luoreng; Da-Wei Wei (Research in Veterinary Science, 2023)

Effect of extracellular polymers in the wastewater on the incorporation of heavy metals with struvite and their adsorption mechanism - Yazhou Wang; Liya Ma; Jinrong Da; Yan Liang; Xiaoning Liu; Jianbo Chang (Journal of Environmental Chemical Engineering, 2023)

Water strider inspired floating solar evaporator with high salt-resistant ability for desalination of contaminated seawater - Yiming Wang; Junjian Zhao; Zhechen Zhang; Jing Xu; Zhi-Da Gao; Yan-Yan Song (Journal of Environmental Chemical Engineering, 2023)

Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook - Ma-Lin Cui; Zi-Xuan Lin; Qing-Fan Xie; Xiao-Yan Zhang; Bing-Qing Wang; Miao-Ling Huang; Da-Peng Yang (Food Chemistry, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Synergism between chikungunya virus infection and rheumatoid arthritis on cytokine levels: Clinical implications? - Luan Araújo Bezerra; Yan Charles da Silva Bastos; Juliana Prado Gonçales; José Valter Joaquim Silva Júnior; Virgínia Maria Barros de Lorena; Angela Luzia Branco Pinto Duarte; Claudia Diniz Lopes Marques; Maria Rosângela Cunha Duarte Coêlho (Brazilian Journal of Microbiology, 2023)

Comparative genomics reveal distinct potential of Tamlana sp. S12 for algal polysaccharide degradation - Hai-Feng Xia; Xiao-Yu Jia; Yan-Xia Zhou; Zong-Jun Du; Da-Shuai Mu; Guan-Jun Chen (Frontiers in Marine Science, 2023)
Introduction Macroalgae contain various polysaccharides that serve as nutrient sources Introduction: Macroalgae contain various polysaccharides that serve as nutrient sources for marine bacteria. Carbohydrate-active enzymes (CAZymes) are the primary feature of marine bacteria that utilize these polysaccharides. In this study, we describe Tamlana sp. S12, a novel strain of marine flavobacteria that can degrade alginate and Laminaria japonica biomass, isolated from the intestines of the sea cucumber Apostichopus japonicas collected at Weihai coast. Methods We sequenced the entire genome of strain S12 and constructed a phylogenetic tree using the core genome sequences of related strains. We determined the enzymatic activity of strain S12 using the DNS method and measured its growth curve under different carbon sources using spectrophotometry. Results Strain S12 degraded dehydrated L. japonica fragments as the sole nutrient source within 48h. Strain S12 harbors a diverse array of CAZymes at multiple polysaccharide utilization loci (PUL). One PUL encoding lyases from PL6, 7, and 17 families may be used for the degradation of alginate. Additionally, strain S12 harbors PULs encoding carrageenan- and agar-targeting CAZymes. Comparative analysis with related flavobacteria from Algibacter , Maribacter , and Zobellia showed shared CAZymes among these strains, potentially derived from a common ancestor and stably maintained within strains. Genomic signatures, algal degradation ability, and CAZyme patterns suggest that strain S12 has the potential to degrade complex algal polysaccharides. Conclusion These results expand our knowledge of CAZymes and enrich our understanding of how marine Flavobacteriaceae adapt to marine algal polysaccharide environments. The availability of the genome of Tamlana sp. S12 will be beneficial for further analyses of marine Flavobacteriaceae.

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

Revealed mechanism of micron-pore size of 3D bio-anode on the behavior of biofilm and system performance in microbial electrochemical system - Jiannan Li; Ye Qiu; Da Li; Jing Wu; Yan Tian; Guohong Liu; Yujie Feng (Chemical Engineering Journal, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

A statistical quantitative analysis of the correlations between socio-demographic characteristics and household occupancy patterns in residential buildings in China - Xue Liu; Shan Hu; Da Yan (Energy and Buildings, 2023)

Gestational exposure to organophosphate esters and adiposity measures of children up to 6 years: Effect modification by breastfeeding - Yafei Chen; Xiaohua Zhang; Ziliang Wang; Zhengwei Yuan; Min Luan; Wei Yuan; Hong Liang; Hexia Chen; Da Chen; Yan Yang; Maohua Miao (International Journal of Hygiene and Environmental Health, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Two new lignans from the herbaceous stems of Ephedra intermedia - Xi-Ling Fan; Yan-Gang Cao; Yan-Ling Liu; Xu Chen; Ying-Jie Ren; Xin-Yi Ma; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Integrated physical approach to assessing urban-scale building photovoltaic potential at high spatiotemporal resolution - Zhaoru Liu; Xue Liu; Haoran Zhang; Da Yan (Journal of Cleaner Production, 2023)

Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides - Hao-Tian Mao; Lun-Xing Chen; Meng-Ying Zhang; Qiu-Yun Shi; Hong Xu; Da-Yan Zhang; Zhong-Wei Zhang; Ming Yuan; Shu Yuan; Huai-Yu Zhang; Yan-Qiu Su; Yang-Er Chen (Environmental Pollution, 2023)

A systematic review of building electricity use profile models - Xuyuan Kang; Jingjing An; Da Yan (Energy and Buildings, 2023)

Janus nanozyme based satellite structure immunosandwich colorimetric strategy for glycoproteins visual detection - Yi-Da Zhang; Chen Ma; Yan-Ping Shi (Chemical Engineering Journal, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Technological development pathway for carbon neutrality in China - Siyue Guo; Yu Liu; Weichen Zhao; Jiaquan Li; Guangwen Hu; Hui Kong; Yifan Gu; Bang Xu; Xiaodan Huang; Yan Zheng; Shihan Zhang; Da Zhang; et al. (Science Bulletin, 2023)

A reliable and effective sample preparation protocol of MALDI-TOF-MSI for lipids imaging analysis in hard and dry cereals - Yan-Xia Zhang; Yi-Da Zhang; Yan-Ping Shi (Food Chemistry, 2023)

Regulation of reactive oxygen species on production, release, and early germination of archeospores in Pyropia yezoensis - Chao-Feng Teng; Da-Hai Gao; Hong-Chang Ding; Xing-Hong Yan (Algal Research, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Identification of Key Genes Associated with Risk and Prognosis of Neuroblastoma - Jiao Zhang; Yahui Han; Dun Yan; Diming Zhou; Xiafei Yuan; Wei Zhao; Da Zhang (Journal of Molecular Neuroscience, 2022)

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

Xenoestrogen Status of Wuling Farm to Surrounding Water Bodies: An Application of Biochemical Parameters Using Onychostoma barbatulum - Lin-Yan Liao; Hui-Ling Cheng; Shu-Yin Wang; Shih-Hsiung Liang; Da-Ji Huang (Journal of Marine Science and Engineering, 2022)
The aim of this study was to apply biochemical parameters to Onychostoma barbatulum to understand whether Wuling Farm activities have caused organic pollution from xenoestrogens to flow into surrounding streams and thereby affected area aquatic ecosystems. Individuals of the Taiwan shovel-jaw carp (O. barbatulum) were collected by fyke netting in the Cijiawan, Kaoshan, and Yusheng Rivers in the protected area of Shei-Pa National Park and in the Ikawan River outside the protected areas from 4–5 June 2015 to 20–21 September 2015. The collected male individuals of O. barbatulum were divided into two groups. In the first group monooxygenase (Mon) activity, glutathione S-transferase (GST) activity, and vitellogenin (VTG) concentration in the liver were measured right after they were captured. Those in the second group were acclimated for 14 days and then exposed to 0 (control) or 10 ng/L 17β-estradiol for 10 days and then measured for changes in Mon, GST, and VTG in their livers. The value of VTG concentrations in O. barbatulum individuals collected from the Ikawan River was 2.12 ± 1.62 μg PO42+/g protein, which was the highest among all samples, followed by those collected from the Yusheng River (0.78 ± 1.00 μg PO42+/g protein). Individuals collected from the Yusheng River had the highest liver Mon activity (4.16 ± 1.08△A650/30 min/g protein) and the highest GST activity (1.58 ± 1.13 △A340/20 min/g protein), followed by those from the Ikawan River (Mon: 3.63 ± 1.13 △A650/30 min/g protein; GST: 1.24 ± 0.73 △A340/20 min/g protein). Comprehensive analyses showed that Mon and GST activities and VTG concentrations in livers measured right after being collected were lower than individuals exposed to 10 ng 17β-estradiol/L in the laboratory. Induced VTG concentrations were 9.87 ± 0.89 μg PO42+/g protein, Mon activity 8.02 ± 1.74 △A650/30 min/g protein, and GST activity 3.24 ± 0.62 △A340/20 min/g protein, indicating that farming activities have not significantly affected these aquatic organisms. However, pollution sources are still releasing pollutants containing xenoestrogens into the Yusheng River and Ikawan River. The impact of xenoestrogens is worthy of continuous long-term follow-up monitoring.

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

A complex slide-buckling-toppling failure of under-dip soft rock slopes - Bin Li; Da Huang; Yan-Zhi Zhu (European Journal of Environmental and Civil Engineering, 2022)

Magnetotactic bacteria in vertical sediments of volcanic lakes in NE China appear Alphaproteobacteria dominated distribution regardless of waterbody types - Tao Liu; Huiyun Da; Shuang Zhang; Weidong Wang; Hong Pan; Lei Yan (World Journal of Microbiology and Biotechnology, 2022)

Designing specific bacterial 16S primers to sequence and quantitate plant endo-bacteriome - Liying Chen; Mengting Zhang; Da Liu; Hongbo Sun; Jianxiang Wu; Yan Huo; Xiaoying Chen; Rongxiang Fang; Lili Zhang (Science China Life Sciences, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Renal tubule ectopic lipid deposition in diabetic kidney disease rat model and in vitro mechanism of leptin intervention - Shasha Liu; Jingjing Da; Jiali Yu; Rong Dong; Jing Yuan; Fuxun Yu; Yan Zha (Journal of Physiology and Biochemistry, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Identification and expression profiling of HSP20 genes in Neoporphyra haitanensis - Ling-Na Peng; Lin-Bin Huang; Tian-Yu Gui; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2022)

Comparative Analysis of Intestinal Characteristics of Largemouth Bass (Micropterus salmoides) and Intestinal Flora with Different Growth Rates - Xin Su; Da Ji; Junjie Yao; Yuanlong Zou; Mengzhi Yan (Fishes, 2022)
To explore the causes of different growth rates among juvenile populations of largemouth bass, in the present study, a batch of largemouth bass juveniles reared under the same conditions were divided into a fast-growing group and a slow-growing group. We used histological, enzymatic and molecular biology methods to analyze and determine their histomorphological changes, digestive enzyme activity and intestinal floral composition. The fast-growing group had a significantly (p ≤ 0.01) greater intestinal fold height and muscle thickness than the slow-growing group. Lipase activity was significantly (p ≤ 0.01) higher in the fast-growing group than in the slow-growing group. Intestinal microbial analysis showed that the relative abundance of Actinobacteria and Halomonas in the fast-growing group was higher than that in the slow-growing group. This research shows that the differentiation of growth rates in juvenile largemouth bass populations is closely related to intestinal fold status, lipase activity, and intestinal flora.

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

Biocompatible self-healing hydrogels based on boronic acid-functionalized polymer and laponite nanocomposite for water pollutant removal - Xue-Ting Wang; Xudong Deng; Tuo-Di Zhang; Xi Zhang; Wen-Pu Shi; Jialiang Lai; Hongwei Zhou; Ya-Jing Ye; Chen-Yan Zhang; Da-Chuan Yin (Environmental Chemistry Letters, 2022)

Experimental study of vertical and batter pile groups in saturated sand using a centrifuge shaking table - Zhang Jian; Li Yurun; Yan Zhixiao; Huang Da; Rong Xian; Liang Yan (Earthquake Engineering and Engineering Vibration, 2022)

Influence of Distal Re-entry Tears on False Lumen Thrombosis After Thoracic Endovascular Aortic Repair in Type B Aortic Dissection Patients: A Computational Fluid Dynamics Simulation - Da Li; Tinghui Zheng; Zhan Liu; Yan Li; Ding Yuan; Yubo Fan (Cardiovascular Engineering and Technology, 2021)

Correction to: TAK1 is involved in sodium L‑lactate‑stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Soil conservation assessment via climate change and vegetation growth scenarios in the Nile River basin - Hua Liu; Yan-xu Liu; Wen-wu Zhao; Da Peng (Journal of Mountain Science, 2021)

Experimental Study on Failure Behaviour of Ligaments Between Strike-Inconsistent Fissure Pairs Under Uniaxial Compression - Da Huang; Zidai Yan; Zhu Zhong; Shilin Luo; Duofeng Cen; Yixiang Song; Dongming Gu (Rock Mechanics and Rock Engineering, 2021)

TAK1 is involved in sodium L-lactate-stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

A new cyclic peptide from the fibrous root of Pseudostellaria heterophylla - Xiao-fei Zhao; Qian Zhang; Han-tao Zhao; Yan-da Zhang; Han-ru Liu; Lu-jiang Yuan; Qian-feng Chen (Natural Product Research, 2020)

The Complete Genome Sequence of a Bacterial Strain with High Alkalic Xylanase Activity Isolated from the Sludge Near a Papermill - Si Chen; Hao Feng; Xin Li; Hong-jun Chao; Jing Wu; Jun Liu; Wen-jun Zhu; Da-zhong Yan (Current Microbiology, 2020)

Numerical simulation of shear wave attenuation in borehole inserted by a horizontal fracture - Binpeng Yan; Weiming Ou; Xingguo Huang; Nuno Vieira da Silva (Acta Geophysica, 2020)

Populeuphrines A and B, two new cembrane diterpenoids from the resins of Populus euphratica - Kai-Xin Liu; Da-Peng Qin; Yan-Xia Zhu; Shao-Xiang Wang; Ya-Bin Jiao; Peng-Ling Ge; Yong-Xian Cheng (Natural Product Research, 2020)

Safety threshold of blasting vibration velocity in foundation excavation of Baihetan super-high arch dam - Wenjun Xia; Wenbo Lu; Gaohui Wang; Peng Yan; Da Liu; Zhendong Leng (Bulletin of Engineering Geology and the Environment, 2020)

Inhibition of orf virus replication in goat skin fibroblast cells by the HSPA1B protein, as demonstrated by iTRAQ-based quantitative proteome analysis - Jun-hong Hao; Han-jin Kong; Ming-hao Yan; Chao-chao Shen; Guo-wei Xu; Da-jun Zhang; Ke-shan Zhang; Hai-xue Zheng; Xiang-tao Liu (Archives of Virology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Alpine Hummocks Drive Plant Diversity and Soil Fertile Islands on the Tibetan Plateau - Hui Zhao; Da Wei; Yan Yan; Jianbo Wu; Xiaodan Wang (Wetlands, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Salt tolerance and exclusion in the mangrove plant Avicennia marina in relation to root apoplastic barriers - Hao Cheng; Anifiok Inyang; Chang-Da Li; Jiao Fei; Yan-Wu Zhou; You-Shao Wang (Ecotoxicology, 2020)

Role of Occlusion Position in Coronary Artery Fistulas with Terminal Aneurysms: A Hemodynamic Perspective - Haoyao Cao; Da Li; Yan Li; Yue Qiu; Jing Liu; Huaxia Pu; Liqing Peng; Tinghui Zheng (Cardiovascular Engineering and Technology, 2020)

Experimental study on the dynamic properties of lime-solidified soft soil under cyclic loading - Guijie Zhao; Huan Yan; Ying Yan; Shaobo Gao; Da Fan; Yang He; Yu Wang (Arabian Journal of Geosciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Geochemical features and potential environmental implications of heavy metals in mining-impacted sediments, south China - Bo Yan; Da-Mao Xu; Tao Chen; ZiAng Yan; Li-li Li (Environmental Science and Pollution Research, 2020)

Detailed Analysis of Lipids in Edible Viscera and Muscles of Cooked Crabs Portunus trituberculatus and Portunus pelagicus - Ting Lu; Yan Shen; Guo-Xin Cui; Fa-Wen Yin; Zhuo-Liang Yu; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2020)

Seasonal Variation of Lipid Profile of Oyster Crassostrea talienwhanensis from the Yellow Sea Area - Yan-Fei Liu; Zi-Xuan Wu; Jing Zhang; Yu-Xin Liu; Zhong-Yuan Liu; Hong-Kai Xie; Kanyasiri Rakariyatham; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2020)

The Cannabinoid Receptor Agonist WIN55,212-2 Ameliorates Hippocampal Neuronal Damage After Chronic Cerebral Hypoperfusion Possibly Through Inhibiting Oxidative Stress and ASK1-p38 Signaling - Da-Peng Wang; Qiao-Li Lv; Qi Lin; Kai Kang; Kai-Yan Jin; Jian Hai (Neurotoxicity Research, 2020)

Targeted selective degradation of Bruton’s tyrosine kinase by PROTACs - Shaodong Liu; Yang Da; Feng Wang; Renjie Yan; Yongzhi Shu; Pei Lin; Jun Lin (Medicinal Chemistry Research, 2020)

Correction to: NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Design, synthesis, and biological evaluation of small molecule PROTACs for potential anticancer effects - Yang Da; Shaodong Liu; Pei Lin; Feng Wang; Renjie Yan; Yongzhi Shu; Jun Lin (Medicinal Chemistry Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Disaster reduction stick equipment: A method for monitoring and early warning of pipeline-landslide hazards - Yan Yan; Da-shen Yang; Dong-xian Geng; Sheng Hu; Zi-ang Wang; Wang Hu; Shu-yao Yin (Journal of Mountain Science, 2019)

Ore genesis and tectonic setting of the Laojiagou porphyry molybdenum deposit, Inner Mongolia, China: evidence from geology, fluid inclusions, H–O isotopes, zircon U–Pb geochronology, and geochemistry - Wen-Hao Tang; Jian Li; Ke-Yong Wang; Shun-Da Li; Wen-Yan Cai; Han-Lun Liu; Yi-Cun Wang (Arabian Journal of Geosciences, 2019)

Complete Genome Sequence of a Chlorobenzene Degrader, Pandoraea pnomenusa MCB032 - Hong-Jun Chao; Yuan-yuan Chen; Jing Wu; Da-Zhong Yan; Ning-Yi Zhou (Current Microbiology, 2019)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Correction to: Occurrence and risk assessment of trace metals and metalloids in sediments and benthic invertebrates from Dianshan Lake, China - Yan Wu; Yihui Zhou; Yanling Qiu; Da Chen; Zhiliang Zhu; Jianfu Zhao; Åke Bergman (Environmental Science and Pollution Research, 2019)

Correction to: Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Index of geoaccumulation and spatial distribution of potentially toxic elements in the Serra Pelada gold mine - Renato Alves Teixeira; Edna Santos de Souza; Mauricio Wilians de Lima; Yan Nunes Dias; Wendel Valter da Silveira Pereira; Antonio Rodrigues Fernandes (Journal of Soils and Sediments, 2019)

Polyhalogenated Carbazoles in Surface Sediment from Sanmen Bay, East China Sea: Spatial Distribution and Congener Profile - Yong Qiu; Kunyan Liu; Shanshan Zhou; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Knockdown of KDM2A inhibits proliferation associated with TGF-β expression in HEK293T cell - Wen-hao Xu; Da-yan Liang; Qi Wang; Jinhua Shen; Qing-Hua Liu; Yong-Bo Peng (Molecular and Cellular Biochemistry, 2019)

Characterization of Glycerophospholipid Molecular Species in Two Species of Arcidaes ( Scapharca subcrenata and Scapharca broughtonii ) - Yan-Fei Liu; Fa-Wen Yin; Yu-Xin Liu; Zi-Xuan Wu; Jing Zhang; Qi Zhao; Kanyasiri Rakariyatham; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Numerical Study of Failure Mechanisms and Control Techniques for a Gob-Side Yield Pillar in the Sijiazhuang Coal Mine, China - Wen-da Wu; Jian-biao Bai; Xiang-yu Wang; Shuai Yan; Shao-xu Wu (Rock Mechanics and Rock Engineering, 2019)

Orange and red carotenoid proteins are involved in the adaptation of the terrestrial cyanobacterium Nostoc flagelliforme to desiccation - Yi-Wen Yang; Yan-Chao Yin; Zheng-Ke Li; Da Huang; Jin-Long Shang; Min Chen; Bao-Sheng Qiu (Photosynthesis Research, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Time Effects on Resting EEG in Children With/Without AD/HD - Da-Wei Zhang; Stuart J. Johnstone; Hui Li; Robert J. Barry; Adam R. Clarke; Qihua Zhao; Yan Song; Lu Liu; Qiujin Qian; Yufeng Wang; Li Sun (Brain Topography, 2019)

Predictive model of aflatoxin contamination risk associated with granary-stored corn with versicolorin A monitoring and logistic regression - Meng Ping Jiang; Shao Yan Zheng; Hao Wang; Shu Yao Zhang; Dong Sheng Yao; Chun Fang Xie; Da Ling Liu (Food Additives & Contaminants: Part A, 2019)

Callus of East Indian sandalwood co-cultured with fungus Colletotrichum gloeosporioides accumulates santalenes and bisabolene - Qingwei Cheng; Yuping Xiong; Meiyun Niu; Yueya Zhang; Haifeng Yan; Hanzhi Liang; Beiyi Guo; Xinhua Zhang; Jaime A. Teixeira da Silva; Youhua Xiong; Guohua Ma (Trees, 2019)

Application of Stable Strontium Isotope Geochemistry and Fluid Inclusion Microthermometry to Studies of Dolomitization of the Deeply Buried Cambrian Carbonate Successions in West-Central Tarim Basin, NW China - Ngong Roger Ngia; Mingyi Hu; Da Gao; Zhonggui Hu; Chun-Yan Sun (Journal of Earth Science, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Upregulated expression of human cathelicidin LL-37 in hypercholesterolemia and its relationship with serum lipid levels - Yun-Xi Li; Bao-Zhen Li; Da-Zun Yan (Molecular and Cellular Biochemistry, 2018)

Spatial distribution and environmental implications of heavy metals in typical lead (Pb)-zinc (Zn) mine tailings impoundments in Guangdong Province, South China - Tao Chen; Chang Lei; Bo Yan; Li-li Li; Da-mao Xu; Guang-Guo Ying (Environmental Science and Pollution Research, 2018)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

Mesozoic and Cenozoic structural deformation in the NW Tarim Basin, China: a case study of the Piqiang–Selibuya Fault - Yong Yang; Wen-Qian Yao; Jia-Jia Yan; Ying Guo; Da-Qing Xie (International Geology Review, 2018)

In Vivo Biocompatibility and Improved Compression Strength of Reinforced Keratin/Hydroxyapatite Scaffold - Jie Fan; Meng-Yan Yu; Tong-da Lei; Yong-Heng Wang; Fu-Yuan Cao; Xiao Qin; Yong Liu (Tissue Engineering and Regenerative Medicine, 2018)

Extraction and Characterization of Phospholipid-Enriched Oils from Antarctic Krill ( Euphausia Superba ) with Different Solvents - Fa-Wen Yin; Da-Yong Zhou; Yan-Fei Liu; Qi Zhao; Zhong-Yuan Liu; Liang Song; Xin Zhou; Jian-Run Zhang; Bei-Wei Zhu (Journal of Aquatic Food Product Technology, 2018)

Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2018)

Multiple strategies for increasing yields of essential oil and obtaining sandalwood terpenoids by biotechnological methods in sandalwood - Yueya Zhang; Haifeng Yan; Meiyun Niu; Qingwei Cheng; Xinhua Zhang; Jaime A. Teixeira da Silva; Guohua Ma (Trees, 2018)

Contaminant characteristics and environmental risk assessment of heavy metals in the paddy soils from lead (Pb)-zinc (Zn) mining areas in Guangdong Province, South China - Da-Mao Xu; Bo Yan; Tao Chen; Chang Lei; Han-Zhi Lin; Xian-Ming Xiao (Environmental Science and Pollution Research, 2017)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Organophosphate Flame Retardants in House Dust from South China and Related Human Exposure Risks - Hongli Tan; Changfeng Peng; Ying Guo; Xiaodong Wang; Yan Wu; Da Chen (Bulletin of Environmental Contamination and Toxicology, 2017)

The Forms of Fluoride in Antarctic Krill ( Euphausia superba ) Oil Extracted with Hexane and its Removal with Different Absorbents - Fa-Wen Yin; Da-Yong Zhou; Yan-Fei Liu; Qi Zhao; Xin Zhou; Liang Song; Lei Qin; Hang Qi; Bei-Wei Zhu (Journal of Aquatic Food Product Technology, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Occurrence and risk assessment of trace metals and metalloids in sediments and benthic invertebrates from Dianshan Lake, China - Yan Wu; Yihui Zhou; Yanling Qiu; Da Chen; Zhiliang Zhu; Jianfu Zhao; Ǻke Bergman (Environmental Science and Pollution Research, 2017)
The present study measured concentrations of Cr, Ni, Cu, Zn, As, Cd, Sb, and Pb in surface sediments and two benthic invertebrate species ( Anodonta woodiana and Bellamya aeruginosa ) collected from Dianshan Lake, located in the Yangtze River Delta. The Dianshan Lake acts as one of the most important drinking water sources to Shanghai, the biggest city in China. Concentrations of trace metals and metalloids ranged from 0.04 mg/kg for Cd to 288.0 mg/kg for Zn. Substantial bioaccumulation in invertebrates was observed for Zn and Cu based on the biota-sediment accumulation factor (BSAF) measurements. The results revealed that concentrations of metals and metalloids in sediments from Dianshan Lake were at the lower end of the range of levels found in other regions of China. The assessment of three significantly inter-related evaluation indices, including the geo-accumulation Index (I geo ), potential ecological risk factor (Er i ), and mean probable effect concentration quotients (Q m-PEC ), suggested that sediment-associated trace elements exhibited no considerable ecological risks in the studied watershed. However, the target hazard quotient and hazard index analysis suggested that selected elements (particularly As) accumulation in edible tissues of benthic invertebrates could pose potential health risks to local populations, especially fishermen. Given that wild aquatic organisms (e.g., fish and bivalves) constitute the diet of local populations as popular food/protein choices, further investigations are needed to better elucidate human health risks from metal and metalloid exposure via edible freshwater organisms.

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Variations and trends of trans-boundary runoff in the longitudinal range-gorge region - Yan-ling Yu; Feng Pan; Xin-you Liu; Wen-hua Chen; Da-ming He (Journal of Mountain Science, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Arctigenin Suppress Th17 Cells and Ameliorates Experimental Autoimmune Encephalomyelitis Through AMPK and PPAR-γ/ROR-γt Signaling - Wen Li; Zhihui Zhang; Kai Zhang; Zhenyi Xue; Yan Li; Zimu Zhang; Lijuan Zhang; Chao Gu; Qi Zhang; Junwei Hao; Yurong Da; Zhi Yao; et al. (Molecular Neurobiology, 2016)

Targeting of water-using networks involving regeneration with a graphical approach - Xiao-Yan Fan; Da-Long Xu; Jian-Feng Zhu; Zhi-Yong Liu (Clean Technologies and Environmental Policy, 2016)

Molecular epidemiology and phylogenetic analysis of HA gene of influenza A(H1N1)pdm09 strain during 2010–2014 in Dalian, North China - Yan Han; Nan Sun; Qiu-yue Lv; Dan-hong Liu; Da-peng Liu (Virus Genes, 2016)

Plant regeneration via direct and callus-mediated organogenesis from leaf explants of Chirita swinglei (Merr.) W. T. Wang - Yulu Chen; Yueya Zhang; Qingwei Cheng; Meiyun Niu; Hanzhi Liang; Haifeng Yan; Xinhua Zhang; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Ag/Ag2SO3 plasmonic catalysts with high activity and stability for CO2 reduction with water vapor under visible light - Da Wang; Yan Yu; Zhipeng Zhang; Huiying Fang; Jianmeng Chen; Zhiqiao He; Shuang Song (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Functional role of an endophytic Bacillus amyloliquefaciens in enhancing growth and disease protection of invasive English ivy (Hedera helix L.) - Marcos Antônio Soares; Hai-Yan Li; Marshall Bergen; Joaquim Manoel da Silva; Kurt P. Kowalski; James Francis White (Plant and Soil, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Aconitum carmichaelii Debeaux, cultivated as a medicinal plant in western China - Ma Yu; Yu-Xia Yang; Xiao-Yan Shu; Jing Huang; Da-Bin Hou (Genetic Resources and Crop Evolution, 2016)

A new triterpenoid saponin from Clinopodium chinense (Benth.) O. Kuntze - Biao Zeng; Guang-Da Liu; Bao-Bao Zhang; Shan-shan Wang; Rui Ma; Bei-Shan Zhong; Bai-qiu He; Yan Liang; Fei-Hua Wu (Natural Product Research, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Late Pleistocene - Holocene slip history of the Langshan-Seertengshan piedmont fault (Inner Mongolia, northern China) from cosmogenic 10Be dating on a bedrock fault scarp - Xiao-ming Shen; De-wen Li; Yun-tao Tian; Yan-wu Lv; Da-wei Li; Yan-feng Li (Journal of Mountain Science, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

The marine redox change and nitrogen cycle in the Early Cryogenian interglacial time: Evidence from nitrogen isotopes and Mo contents of the basal Datangpo Formation, northeastern Guizhou, South China - Wei Wei; Dan Wang; Da Li; Hongfei Ling; Xi Chen; Guangyi Wei; Feifei Zhang; Xiangkun Zhu; Bin Yan (Journal of Earth Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Strategy to Suppress Oxidative Damage-Induced Neurotoxicity in PC12 Cells by Curcumin: the Role of ROS-Mediated DNA Damage and the MAPK and AKT Pathways - Xiao-yan Fu; Ming-feng Yang; Ming-zhi Cao; Da-wei Li; Xiao-yi Yang; Jing-yi Sun; Zong-yong Zhang; Lei-lei Mao; Shuai Zhang; Feng-ze Wang; Feng Zhang; Cun-dong Fan; et al. (Molecular Neurobiology, 2016)

Identification and characterization of eighteen polymorphic microsatellite loci for a threatened freshwater fish, Botia superciliaris - FEI XIONG; HONG-YAN LIU; XIN-BIN DUAN; DA-QING CHEN (Journal of Genetics, 2015)

Travel motivation of domestic tourists to the Changbai Mountain Biosphere Reserve in Northeastern China: A comparative study - Xiao-ping Gu; Bernard J. Lewis; Yan-quan Li; Da-pao Yu; Li Zhou; Wang-ming Zhou; Sheng-nan Wu; Li-min Dai (Journal of Mountain Science, 2015)

Multiple glacial refugia for cool‐temperate deciduous trees in northern East Asia: the Mongolian oak as a case study - Yan‐Fei Zeng; Wen‐Ting Wang; Wan‐Jin Liao; Hong‐Fang Wang; Da‐Yong Zhang (Molecular Ecology, 2015)
In East Asia, temperate forests are predicted to have retracted southward to c . 30° N during the last glacial maximum ( LGM ) based on fossil pollen data, whereas phylogeographic studies have often suggested glacial in situ survival of cool‐temperate deciduous trees in their modern northern ranges. Here we report a study of the genetic diversity and structure of 29 natural Mongolian oak ( Quercus mongolica ) populations using 19 nuclear simple sequence repeat ( nSSR ) loci and four chloroplast DNA fragments. Bayesian clustering analysis with nSSR s revealed five groups, which were inferred by approximate Bayesian computation ( ABC ) to have diverged in multiple refugia through multiple glacial–interglacial cycles. Analysis of chloroplast DNA variation revealed four lineages that were largely but incompletely geographically disjunct. Ecological niche modelling (ENMs) indicated a southward range shift of the oak's distribution at the LGM , although high suitability scores were also evident in the Changbai Mts. (Northeast China), the Korean Peninsula, areas surrounding the Bohai Sea, and along the coast of the Russian Far East. In addition, endemic chloroplast DNA haplotypes and nuclear lineages occurred in high‐latitude northern areas where the ENM predicted no suitable habitat. The combined evidence from nuclear and chloroplast DNA , and the results of the ENM clearly demonstrate that multiple northern refugia, including cryptic ones, were maintained across the current distributional range of the Mongolian oak during the LGM or earlier glacial periods. Though spatially limited, postglacial expansions from these refugia have led to a pattern of decreased genetic diversity with increasing latitude.

Protective effect of low dose gadolinium chloride against isoproterenol-induced myocardial injury in rat - Yuan-Yuan Zheng; Hai-Hong Zhang; Xin-Xin Yan; Min Chen; Tian-Yu Qi; Lan-E Zhang; Da-Li Luo (Apoptosis, 2015)

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

PPARα Agonist Fenofibrate Ameliorates Learning and Memory Deficits in Rats Following Global Cerebral Ischemia - Ai-Guo Xuan; Yan Chen; Da-Hong Long; Meng Zhang; Wei-Dong Ji; Wen-Juan Zhang; Ji-Hong Liu; Le-Peng Hong; Xiao-Song He; Wen-Liang Chen (Molecular Neurobiology, 2015)

Laparoscopic versus open distal pancreatectomy for benign or premalignant pancreatic neoplasms: A two-center comparative study - Jia-fei Yan; Tian-tao Kuang; Da-yong Ji; Xiao-wu Xu; Dan-song Wang; Ren-chao Zhang; Wei-wei Jin; Yi-ping Mou; Wen-hui Lou (Journal of Zhejiang University-SCIENCE B, 2015)

Escitalopram Ameliorates Forskolin-Induced Tau Hyperphosphorylation in HEK239/tau441 Cells - Qing-Guo Ren; Yan-Juan Wang; Wei-Gang Gong; Qi-Da Zhou; Lin Xu; Zhi-Jun Zhang (Journal of Molecular Neuroscience, 2015)

Degradation of florfenicol in water by UV/Na2S2O8 process - Yu-qiong Gao; Nai-yun Gao; Yang Deng; Da-qiang Yin; Yan-sen Zhang (Environmental Science and Pollution Research, 2015)

Citalopram Attenuates Tau Hyperphosphorylation and Spatial Memory Deficit Induced by Social Isolation Rearing in Middle-Aged Rats - Qing-Guo Ren; Wei-Gang Gong; Yan-Juan Wang; Qi-Da Zhou; Zhi-Jun Zhang (Journal of Molecular Neuroscience, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

Biodegradation of hexachlorobenzene by a constructed microbial consortium - Da-Zhong Yan; Ling-Qi Mao; Cun-Zhi Li; Jun Liu (World Journal of Microbiology and Biotechnology, 2015)

Tree architecture varies with forest succession in evergreen broad-leaved forests in Eastern China - Xiao-Dong Yang; En-Rong Yan; Scott X. Chang; Liang-Jun Da; Xi-Hua Wang (Trees, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

N-3 polyunsaturated fatty acids intake and risk of colorectal cancer: meta-analysis of prospective studies - Guo-Chong Chen; Li-Qiang Qin; Da-Bing Lu; Tie-Mei Han; Yan Zheng; Guo-Zhang Xu; Xiao-Huai Wang (Cancer Causes & Control, 2015)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Effects of heating conditions on fatty acids and volatile compounds in foot muscle of abalone Haliotis discus hannai Ino - Hong-Xu Wang; Lei Qin; Yan Wang; Da-Yong Zhou; Shuang Song; Xu-Song Wang; Bei-Wei Zhu (Fisheries Science, 2014)

A CMS-Related Gene, Ψatp6-2, Causes Increased ATP Hydrolysis Activity of the Mitochondrial F1Fo-ATP Synthase and Induces Male Sterility in Pepper (Capsicum annuum L.) - Jiao-Jiao Ji; Wei Huang; Da-Wei Li; Yan-Xu Yin; Wei-Guo Chai; Zhen-Hui Gong (Plant Molecular Biology Reporter, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Coal-burning endemic fluorosis is associated with reduced activity in antioxidative enzymes and Cu/Zn-SOD gene expression - Qi Wang; Kang-ping Cui; Yuan-yuan Xu; Yan-ling Gao; Jing Zhao; Da-sheng Li; Xiao-lei Li; Hou-jin Huang (Environmental Geochemistry and Health, 2014)

Effects of submerged macrophytes on the abundance and community composition of ammonia-oxidizing prokaryotes in a eutrophic lake - Da-yong Zhao; Juan Luo; Jin Zeng; Meng Wang; Wen-ming Yan; Rui Huang; Qinglong L. Wu (Environmental Science and Pollution Research, 2014)

Molecular characterization and expression analysis of a KIFC1-like kinesin gene in the testis of Eumeces chinensis - Jian-Rao Hu; Mei Liu; Da-Hui Wang; Yan-Jun Hu; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Study on the In Vitro Effects of the Mixtures of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals on Ethoxyresorufin-O-Deethylase (EROD) Activity in Mossambica tilapia Liver - Da Xiong Han; Hai Yan Wang; Hong Wei Yue; Su Min Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

Nicotine Addiction Reduces the Large-Conductance Ca2+-activated Potassium Channels Expression in the Nucleus Accumbens - Lan Ma; Yu-Mei Wu; Yan-Yan Guo; Qi Yang; Bin Feng; Qian Song; Shui-Bing Liu; Da-qing Zhao; Ming-Gao Zhao (NeuroMolecular Medicine, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Auto- and Cross-repression of Three Arabidopsis WRKY Transcription Factors WRKY18, WRKY40, and WRKY60 Negatively Involved in ABA Signaling - Lu Yan; Zhi-Qiang Liu; Yan-Hong Xu; Kai Lu; Xiao-Fang Wang; Da-Peng Zhang (Journal of Plant Growth Regulation, 2013)

Development of microsatellite markers for Leptobotia rubrilaris, a threatened fish species in the Yangtze River - Xin Bin Duan; Hong Yan Liu; Fei Xiong; Da Qing Chen (Conservation Genetics Resources, 2013)

A gain-of-function mutation in IAA8 alters Arabidopsis floral organ development by change of jasmonic acid level - Jing Wang; Da-Wei Yan; Ting-Ting Yuan; Xiang Gao; Ying-Tang Lu (Plant Molecular Biology, 2013)

Expression of OsMSR3 in Arabidopsis enhances tolerance to cadmium stress - Yanchun Cui; Guoyun Xu; Manling Wang; Yan Yu; Mingjuan Li; Pedro S. C. Ferreira da Rocha; Xinjie Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

ATP Regulates Sodium Channel Kinetics in Pancreatic Islet Beta Cells - Na Zou; Xiao Wu; Yan-Yan Jin; Meng-Zao He; Xin-Xin Wang; Li-Da Su; Marjan Rupnik; Zhen-Yong Wu; Li Liang; Ying Shen (The Journal of Membrane Biology, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Roles of the different components of magnesium chelatase in abscisic acid signal transduction - Shu-Yuan Du; Xiao-Feng Zhang; Zekuan Lu; Qi Xin; Zhen Wu; Tao Jiang; Yan Lu; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Sprout vacuum-infiltration: a simple and efficient agroinoculation method for virus-induced gene silencing in diverse solanaceous species - Hua-xue Yan; Da-qi Fu; Ben-zhong Zhu; Hai-ping Liu; Xiao-ying Shen; Yun-bo Luo (Plant Cell Reports, 2012)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Characterization and expression pattern of KIFC1-like kinesin gene in the testis of the Macrobrachium nipponense with discussion of its relationship with structure lamellar complex (LCx) and acroframosome (AFS) - Yan-Ting Wang; Huan Mao; Cong-Cong Hou; Xiao Sun; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

A first set of polymorphic microsatellite loci isolated from Rhinogobio cylindricus - Hong Yan Liu; Fei Xiong; Xin Bin Duan; Da Qing Chen; Shao Ping Liu; Fan Rrong Zhang; Dong Yang; Lai Ning Yu (Conservation Genetics Resources, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Costs of inflorescence longevity for an Asian fig tree and its pollinator - Yuan Zhang; Da-Rong Yang; Yan-Qiong Peng; Stephen G. Compton (Evolutionary Ecology, 2012)

Effects of average velocity on the growth and surface topography of biofilms attached to the reclaimed wastewater drip irrigation system laterals - Gui Bing Li; Yun Kai Li; Ting Wu Xu; Yao Ze Liu; Hai Jin; Pei Ling Yang; Da Zhuang Yan; Shu Mei Ren; Zhi Fang Tian (Irrigation Science, 2012)

Isolation and characterization of polymorphic microsatellite loci from elongate loach (Leptobotia elongate), a threatened fish species endemic to the Yangtze River - Hong Yan Liu; Fei Xiong; Xin Bin Duan; Da Qing Chen (Conservation Genetics Resources, 2012)

The effect of sevoflurane on the expression of M1 acetylcholine receptor in the hippocampus and cognitive function of aged rats - Sheng Peng; Yan Zhang; Guo-Jun Li; Deng-Xin Zhang; Da-Peng Sun; Qiang Fang (Molecular and Cellular Biochemistry, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Gastrodin protects against cardiac hypertrophy and fibrosis - Chunming Shu; Changgui Chen; Da-Ping Zhang; Haipeng Guo; Heng Zhou; Jing Zong; Zhouyan Bian; Xuan Dong; Jia Dai; Yan Zhang; Qizhu Tang (Molecular and Cellular Biochemistry, 2012)

Surface topographic characteristics of suspended particulates in reclaimed wastewater and effects on clogging in labyrinth drip irrigation emitters - Yun Kai Li; Yao Ze Liu; Gui Bing Li; Ting Wu Xu; Hai Sheng Liu; Shu Mei Ren; Da Zhuang Yan; Pei Ling Yang (Irrigation Science, 2012)

Evaluation of Left Ventricular Twist in Acute Myocardial Infarction Patients Using Speckle Tracking Imaging - Da-lin Jia; Chun-yan Ma; Shuang Liu; Lu-fan Sun (Cell Biochemistry and Biophysics, 2011)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

Ototoxic destruction by co-administration of kanamycin and ethacrynic acid in rats - Hong Liu; Da-lian Ding; Hai-yan Jiang; Xue-wen Wu; Richard Salvi; Hong Sun (Journal of Zhejiang University-SCIENCE B, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Development of transgenic zooplankton Artemia as a bioreactor to produce exogenous protein - Shih-Hung Chang; Ben-Chang Lee; Yan-Da Chen; Yin-Chou Lee; Huai-Jen Tsai (Transgenic Research, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

The effect of sevoflurane anesthesia on cognitive function and the expression of Insulin-like Growth Factor-1 in CA1 region of hippocampus in old rats - Sheng Peng; Yan Zhang; Da-Peng Sun; Deng-Xin Zhang; Qiang Fang; Guo-Jun Li (Molecular Biology Reports, 2011)

Polymorphisms in the calcineurin genes are associated with the training responsiveness of cardiac phenotypes in Chinese young adults - Zi-Hong He; Yang Hu; Yan-Chun Li; Da-Peng Bao; Jonatan R. Ruiz; Alejandro Lucia (European Journal of Applied Physiology, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

The reproductive success of Ficus altissima and its pollinator in a strongly seasonal environment: Xishuangbanna, Southwestern China - Yan-Qiong Peng; Stephen G. Compton; Da-Rong Yang (Plant Ecology, 2010)

Amino Acid Homochirality may be Linked to the Origin of Phosphate-Based Life - Da Xiong Han; Hai Yan Wang; Zhi Liang Ji; An Fu Hu; Yu Fen Zhao (Journal of Molecular Evolution, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

The effects of CYP2C9 and CYP2C19 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of glipizide in Chinese subjects - Bo Tan; Yi-Fan Zhang; Xiao-Yan Chen; Xiao-Hua Zhao; Guo-Xin Li; Da-Fang Zhong (European Journal of Clinical Pharmacology, 2010)

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes - Da Chun Chen; Jing Wang; Bo Wang; Sheng Chang Yang; Chong Xi Zhang; You Lan Zheng; Yan Li Li; Ning Wang; Ke Bing Yang; Mei Hong Xiu; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2009)

Isolation and characterization of microsatellite markers for Glytothorax zanaensis - Shao-Ping Liu; Xi-Ping Yuan; Deng-Qiang Wang; Xing-Jian Yue; Yan Zhang; Ke Wang; Xin-Bin Duan; Da-Qing Chen (Conservation Genetics Resources, 2009)

Coevolution of reproductive characteristics in three dioecious fig species and their pollinator wasps - Wen J. Ma; Yan Q. Peng; Da-R. Yang; Jun M. Guan (Symbiosis, 2009)

Gender differences in the prevalence, risk and clinical correlates of tardive dyskinesia in Chinese schizophrenia - Xiang Yang Zhang; Da Chun Chen; Ling Yan Qi; Fang Wang; Mei Hong Xiu; Song Chen; Gui Ying Wu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Molecular actions guiding neural regeneration in planarian - Yan-Fen Zhang; Bo-Ping Ye; Da-Yong Wang (Neuroscience Bulletin, 2008)

Hyper-spectral remote sensing to monitor vegetation stress - Hong-Yan Ren; Da-Fang Zhuang; Jian-Jun Pan; Xue-Zheng Shi; Hong-Jie Wang (Journal of Soils and Sediments, 2008)

Degradation of cyclohexylamine by a new isolate of Pseudomonas plecoglossicida - Yi Shen; Da-Zhong Yan; Xiang-Qun Chi; Yan-Yan Yang; David J. Leak; Ning-Yi Zhou (World Journal of Microbiology and Biotechnology, 2008)

Analysis of quantitative trait loci underlying the period of reproductive growth stages in soybean (Glycine max [L.] Merr.) - Da-Wei Xin; Hong-Mei Qiu; Da-Peng Shan; Cai-Yun Shan; Chun-Yan Liu; Guo-Hua Hu; Christian Staehelin; Qing-Shan Chen (Euphytica, 2008)

Virulence of H5N1 avian influenza virus enhanced by a 15-nucleotide deletion in the viral nonstructural gene - Jin-Xue Long; Da-Xin Peng; Yu-Liang Liu; Yan-Tao Wu; Xiu-Fan Liu (Virus Genes, 2008)

Functional expression of an earthworm fibrinolytic enzyme in Escherichia coli - Da-hui Li; Wei Tong; Yan-fang Yang (World Journal of Microbiology and Biotechnology, 2008)

AICAR induces phosphorylation of AMPK in an ATM-dependent, LKB1-independent manner - Yan Sun; Katie E. Connors; Da-Qing Yang (Molecular and Cellular Biochemistry, 2007)

Synthesis of 1H-imidazo[1,2-b]-1,2,4-triazol-6-amines via multicomponent reaction - Yan Huang; Xiu-Qin Hu; Da-Peng Shen; Yong-Fei Chen; Peng-Fei Xu (Molecular Diversity, 2007)

Co-transformation of gene expression cassettes via particle bombardment to generate safe transgenic plant without any unwanted DNA - Yan Zhao; Qian Qian; Hui-Zhong Wang; Da-Nian Huang (In Vitro Cellular & Developmental Biology - Plant, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Study progress in therapeutic effects of traditional Chinese medicine monomer in severe acute pancreatitis - Xi-ping Zhang; Da-ren Liu; Yan Shi (Journal of Zhejiang University-SCIENCE B, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Characterization of on-road CO, HC and NO emissions for petrol vehicle fleet in China city - Hui Guo; Qing-yu Zhang; Yao Shi; Da-hui Wang; Shu-ying Ding; Sha-sha Yan (Journal of Zhejiang University-SCIENCE B, 2006)

The style–length of the female florets and their fate in two dioecious species of Xishuangbanna, China - Zhang-Hong Shi; Da-Rong Yang; Yan-Qiong Peng (Trees, 2006)

Two new species of egg parasitoids (hymenoptera: Encyrtidae) of wood-boring beetle pests from China - Yan-Zhou Zhang; Da-Wei Huang; Tong-Hai Zho; Hou-Ping Liu; Leah S. Bauer (Phytoparasitica, 2005)

Cloning and Characterization of a ?3 Tubulin cDNA From the Small Brown Planthopper, Laodelphax striatellus - Jian-Guo Wen; Jian Yan; Jia Xu; Da-Leng Shen (Biochemical Genetics, 2005)

Phylogenetic Analysis Reveals that a Dwarfing Disease on Different Cereal Crops in China is due to Rice Black Streaked Dwarf Virus (RBSDV) - Feng-wei Bai; Jian Yan; Zhi-cai Qu; Hong-wei Zhang; Jia Xu; Ming-ming Ye; Da-leng Shen (Virus Genes, 2002)

Internet based environmental monitoring information system and its application in Yili Prefecture - Deng Xiang-zheng; Liu Ji-yuan; Zhuang Da-fang; Zhan Jin-yan (Journal of Geographical Sciences, 2002)

The global rainforest mapping project JERS-1: a paradigm of international collaboration for monitoring land cover change - Deng Xiang-zheng; Zhan Jin-yan; Liu Ji-yuan; Zhuang Da-fang (Journal of Geographical Sciences, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)